Development of recombinant subunit vaccines against Flavobacterium covae and Flavobacterium columnare in grass carp (Ctenopharyngodon idellus): Evaluation of protective efficacy and antibody immune response - Zhongning He; Rui Han; Huicheng Wu; Xueming Dan; Yanwei Li; Zequan Mo (Aquaculture, 2027)

Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Freeze-thaw stability of frozen dough containing superheated steam-treated wheat flour: insights into gluten protein aggregation, structural interactions, and network integrity - Xuepan Qi; Ying Wang; Chang Han; Yamei Jin; Dan Xu; Fengfeng Wu; Qiyan Zhao; Xueming Xu (Food Hydrocolloids, 2026)

Cadmium-associated cognitive impairment in adults: Proteomics-guided blood-based risk stratification with external validation and rat multimodal corroboration - Hao Gao; Hui Liu; Sheng Wan; Zhaokui Dan; Jianjun Xiong; Zelong Xing; Yinghui Yin; Feng Han; Yong Yang; Maoqin Tian; Qiwen Chen; Zhijian Hu; et al. (Environmental Pollution, 2026)

Flexural performance and calculations of concrete-encased square concrete-filled steel tubular (CFST) hybrid structures - Dan-Yang Ma; Jie Gong; Lin-Hai Han; Long-Hui Du (Engineering Structures, 2026)

Defect-engineered Cu-TCPP/ZIF-L nanosheet-modified PVDF membrane with enhanced water purification and dye removal performance - Yiming Zhao; Jingyuan Zhang; Junmei Liu; Jiatong Han; Dan Xu; Jing Wang; Fengzhi Lyu; Lin Qin; Donghui Xu; Ge Chen; Guangyang Liu (Chemical Engineering Journal, 2026)

Mitigation of antibiotic resistance risk in aerobic sludge by zero-valent iron: From pathogen reduction to conjugation inhibition and network weakening - Ying Wu; Lin Zhu; Guoping Lin; Xuezhu Han; Jingpeng Li; Jiaming Yi; Dan Huang; Meizhen Wang (Bioresource Technology, 2026)

Bio-organic fertilizer improves soil carbon sequestration via macroaggregate formation in intensive tomato cultivation system - Lijun Ren; Roland Bol; Lili Dong; Yanyu Han; Dan Wei; Hongtao Zou; Yulong Zhang (Soil and Tillage Research, 2026)

Direct electrochemical regeneration of cathode materials from spent lithium-ion batteries: Progress, challenges, and sustainable perspectives - Pengcheng Liu; Haoran Ren; Li Xiao; Pan Tang; Like Zhang; Han Chen; Ruizhi Zhang; Tiansheng Li; Dan Xue; Sheqiang Niu (Journal of Environmental Chemical Engineering, 2026)

Synergistic vacuum steam pulse blanching and gliding arc cold plasma pretreatment enhances drying efficiency and folate retention in Yardlong bean pods - Samuel Ariyo Okaiyeto; Fan Yang; Dan Liu; Lei Fu; Shi-Han Yu; Xiao-Xiao Niu; Feng-Lun Zhang; Cheng Zhang; Feng-Kui Xiong; Mohsen Mokhtarian; Weiqiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Non-covalent interactions between electroactivated soybean protein isolate and naringin: Structure, functionality and molecular docking - Qianzhu Qin; Weining Wang; Xiue Han; Cuiping Han; Dianyu Yu; Lianzhou Jiang; Dan Feng (Food Chemistry, 2026)

Cryoprotective effect of trehalose on wheat glutenin: Structural, rheological, and molecular insights - Dan Zhang; Xiao-Shan Chen; Wen-Hui Zhang; Zi-Hao Lu; Han Tao; Wan-Hao Cai (Food Hydrocolloids, 2026)

Detection and variation trends of microplastics in edible oils during storage - Chenxin Huang; Jinrui Han; Chongyang Liu; Keqiang Huang; Dan Huang; Xiuzhu Yu (Food Control, 2026)

Synergistic ion-flux homogenization and localized electronic modulation via a mesoporous-quantum hybrid architecture to mitigate cathode–anode cross-talk in aqueous zinc-ion batteries - Le Li; Yue Shi; Dan Zhang; Chao Tan; Xiyan Wei; Hengyuan Hu; Jingwei Wang; Yongqiang Ji; Meisheng Han (Chemical Engineering Journal, 2026)

Metal Bi-coupled chiral nanoscale structures enhance spin-polarized electrons to promote photocatalytic CO2 reduction - Dan Wu; Yanni Lang; Liang Xu; Qiyuexin Wang; Qiu Fu; Bingli Li; Xinye Zhao; Zhaoyi Yin; Yongjin Li; Dacheng Zhou; Yangke Cun; Zhiguo Song; et al. (Chemical Engineering Journal, 2026)

Element substitution engineering of Li3VO4: Exposing high-activity (110) facets for stable interface and superior lithium storage - Huan Liu; Zhaozhao Han; Honglei Zhao; Andong Lin; Dan Zhang; Huaifang Zhang; Jianchuan Wang; Yuanyuan Feng (Chemical Engineering Journal, 2026)

Transcriptome and metabolome analysis reveals that cuproptosis in bovine cumulus cells triggers the intercellular transmission of senescence and mitochondrial dysfunction to impair oocyte quality - Hong Xu; Tian Tian; Dan Xu; Xiaoxue Du; Rui Su; Jinghong Liang; Ying Liu; Yuqing Zhang; Chang Liu; Shuang Liang; Qingying Li; Deli Ding; et al. (Theriogenology, 2026)

Numerical investigation on the influence of interstage leakage in a high-speed low-flow two-stage centrifugal refrigeration compressor - Yafei Duan; Dan Liu; Han Chen; Guang Xi (International Journal of Refrigeration, 2026)

Contributions of superheated steam-treated gluten and starch to the freeze-thaw stability of frozen dough: Evidence from component-reconstituted substitution systems - Xuepan Qi; Ying Wang; Chang Han; Yamei Jin; Dan Xu; Fengfeng Wu; Huang Zhang; Xueming Xu (Food Bioscience, 2026)

Intensified rainfall seasonality and elevated nitrogen deposition reduce soil phosphorus availability in a subtropical forest: Linkages to functional microbes and enzyme kinetics - Zhiming Guo; Anna Gunina; Qingshui Yu; Jianbo Fang; Jinhong He; Xiuling Ni; Yanxia Nie; Xiaoge Han; Dan He; Muhammed Mustapha Ibrahim; Xiangping Tan; Weijun Shen (Applied Soil Ecology, 2026)

Synthesis and antifungal activity evaluation of flavonol derivatives containing an imidazolidinone moiety - Qingxue Hu; Xiaoting Geng; Xiaoyan Pan; Dan Shen; Han Yang; Fang Tian; Mingman Sun; Lang Xing; Ying Yang; Wei Xue (Molecular Diversity, 2026)

Occurrence and distribution of short-chain chlorinated paraffins (SCCPs) in sediments from mariculture bays in northern China - Feiyao Lu; Junhui Chen; Dan Fu; Xueting Zhang; Haoshun Zhang; Tongzhu Han; Xiuping He (Regional Studies in Marine Science, 2026)

Sustainable synthesis of cathode precursors from spent lithium-ion batteries by IoT–holographic twin integration: Process optimization and electrochemical performance evaluation - Dan Luo; Han Zheng; Jan Pan; Wei Sun (Journal of Environmental Chemical Engineering, 2026)

A comparative bioprocess for nutrient reclamation: Suspended versus immobilized Virgibacillus salexigens XYD drives struvite recovery from eutrophic saline water - Na Guo; Yueming Zhao; Shuqi Wang; Yanhong Zhao; Yudong Xu; Memon Kashif Ali; Huaxiao Yan; Hui Zhao; Zuozhen Han; Maurice E. Tucker; Chao Han; Yanyang Zhao; et al. (Journal of Environmental Management, 2026)

A loofah-based microalgae-bacteria symbiosis drives efficient nutrient removal from low-C/N wastewater: high biomass characterization and mechanism insights - Zhuochao Liu; Meiqi Ren; Han Ji; Hongli Lu; Liming Yang; Dan Cui; Yongzhen Peng (Environmental Research, 2026)

Host-guest construction of hyperbranched poly(quaternary ammonium) triple-action antibacterial coating - Jin Han; Yuehua Tang; Huixin Zhu; Dan Wu; Lei Wang; Kun Shen; Xiaoxue Yin; Zhenping Zhao; Tongdong Shen; Boshi Yu; Dong Xu; Qingquan Xue (Chemical Engineering Journal, 2026)

Influence of storing muscle tissue in the cold on in vitro myogenic cell line development from the black sea bream (Acanthopagrus schlegelii) - Eun Soo Jeong; Dan Hee Han; Seung Pyo Gong (Fish Physiology and Biochemistry, 2026)

Determination of short-chain chlorinated paraffins in marine sediment by automated online solid phase extraction coupled to liquid chromatography-high-resolution mass spectrometry - Feiyao Lu; Dan Fu; Xiuping He; Xueting Zhang; Haoshun Zhang; Tongzhu Han; Junhui Chen (Analytica Chimica Acta, 2026)

Two new protoflavonoids from Polytrichum commune and their cytotoxicity against human gastric cancer cells - Jing-jing Dong; Dan-rui Han; Hao Cheng; Xu-liu Shi; Dong-Lai Ma; Jian-kun Yan; Xu-Hong Duan (Natural Product Research, 2026)

A comprehensive PTM atlas of Dermatophagoides farinae reveals an acylation-dominated landscape of allergens - Dan Zeng; Xinhui Gong; Ying Zhou; Lingli Han; Panpan Han; Cunyin Yuan; Dongmei Zhou; Ximeng Ma; Yubao Cui (Science China Life Sciences, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Experimental study on the characteristics of vortex-induced vibrations of a two-degree-of-freedom cylinder near a wall at high Reynolds numbers - Junlong Su; Xiangxi Han; Haonan Guo; Yunfu Liu; Fenjie Pei; Shuwen Wang; Di Ren; Zhanbin Meng; Dan Chen (Ocean Engineering, 2026)

Microplastics and tire wear particles in aquatic environment: A comparative review on generation, characteristics and environmental behavior - Wenlong Zhang; Tengyue Zhang; Dan Shao; Jie Han; Hongjie Wang (NanoImpact, 2026)

Physiological, biochemical and metabolomic analysis revealed the mechanism of selenium alleviating copper stress in Nicotiana tabacum L. - Bingjie Yu; Hang Wang; Mengze Li; Kai Zhang; Ye Xue; Jiashu Tian; Huanyu Teng; Wuxing Huang; Dan Han; Bingjun Dang; Zicheng Xu; Jiayang Xu; et al. (Journal of Environmental Sciences, 2026)

Experimental behaviour of concrete-encased square concrete-filled steel tubular (CFST) hybrid structure subjected to axial compression - Dan-Yang Ma; Long-Hui Du; Lin-Hai Han (Engineering Structures, 2026)

Detachable TMSD-CRISPR for programmable and highly specific discrimination of DNA/RNA mutations - Yiqi Zhang; Wang Luo; Yaoyi Zhang; Yu He; Li Zhang; You Wu; Kejia Wu; Hongyan Yu; Xiaole Han; Na Yin; Jiu Pu; Dan Bai; et al. (Chemical Engineering Journal, 2026)

Graphitization-driven interfacial polarization and conductivity in core–shell Fe3O4@hydrochar composites achieving high-performance electromagnetic wave absorption - Lin Wang; Yingshan Deng; Zurong Zhu; Dan Michelle Wang; Dafu Chen; Guanghui Bai; Zhongyi Feng; Yao Han; Yueyao Liu; Jinxia Zhai; Chengyun Ning; Zhengao Wang (Chemical Engineering Journal, 2026)

Bio-organic fertilizer regulates nutrient accumulation and microbial communities across soil aggregate in intensive vegetable production system - Lijun Ren; Lili Dong; Yanyu Han; Qingfeng Fan; Dan Wei; Hongtao Zou; Yulong Zhang (Plant and Soil, 2026)

Ethyl ferulate attenuates allergic asthma via inhibiting macrophage M2 polarization through STAT6/IRF4 pathway - Longlong Ge; Weizhen Chen; Shuguang Han; Huan Yang; Mingchen Du; Shengpeng Li; Xinran Bai; Peilin Zhao; Dan Chen; Qingfeng Pang; Yaxian Wu (Inflammation Research, 2026)

An integrated shoelace–power law preprocessing workflow for supporting ship-specific wind load assessment during berthing - Liang Ma; Yanru Han; Yuanyuan Chen; Zhenkai Huang; Yu Zhang; Liang Cao; Jianing Dan; Zhaorui Li (Frontiers in Marine Science, 2026)
Wind loads are critical safety concerns for ship berthing and mooring operations in ports. Existing standard methods for wind load assessment often adopt simplified geometric assumptions and fixed wind shear parameters, lacking ship-specific and loading-adaptive capabilities which hinders the practical implementation of the One Ship One Calculation (OSOC) concept in ship wind load assessment. This study proposes an integrated Shoelace-Power Law Model (S-PLM) as a preprocessing workflow for ship windage geometry analysis and height-consistent equivalent wind speed estimation. The workflow combines polygon area calculation via the shoelace algorithm, loading-dependent geometric centroid calculation, and power-law-based vertical wind speed conversion. Validation against the OCIMF standard method shows better agreement in windage area (MAPE = 0.63%) and acceptable deviations in equivalent wind speed across different vessels and loading conditions. Sensitivity analysis of the power-law exponent (α = 0.10–0.25) confirms controllable parameter influence on model outputs. The proposed S-PLM provides reliable, ship-specific preprocessing inputs for subsequent wind load evaluation, supporting refined operational risk assessment during berthing.

Freeze-thaw stability of frozen dough containing superheated steam-treated wheat flour: Evidence from water states and starch properties - Xuepan Qi; Chang Han; Ying Wang; Yamei Jin; Dan Xu; Fengfeng Wu; Xueming Xu (Food Hydrocolloids, 2026)

Cooling characteristics of the dual-layer ventilation slope and underlying permafrost response process of the railbed - Zhenyu Zhang; Qihao Yu; Fenglei Han; Tianchun Dong; Dan Wang; Kun Chen; Zhaohui Sun; Shenglin Wang (Cold Regions Science and Technology, 2026)

The biocontrol potential of volatile organic compounds produced by Bacillus subtilis KRS015 against plant pathogenic fungi Botrytis cinerea - Jiaqi Hu; He Zhu; Jian Song; Jieyin Chen; Dan Wang; Dongfei Han (Journal of Plant Diseases and Protection, 2026)

Prevalence and Molecular Characterization of Entamoeba spp. in Pigs in Shanxi Province, North China - Ze-Dong Zhang; Han-Dan Xiao; Dong-Yang Wang; Zi-Rui Wang; Xun-Zhi Liu; Nan Su; Xing-Quan Zhu; Qing Liu; Wen-Wei Gao (Acta Parasitologica, 2026)

Source-sink dynamics of coastal blue carbon: a review of mechanisms and drivers - Meihong Ge; Jinfeng Du; Yunxiao Han; Lehong Chen; Xuefeng Xu; Yonglian Wang; Changbo Zhong; Dan Feng; Xiaoyan Wu (Frontiers in Marine Science, 2026)
Within the context of global climate change, coastal blue carbon ecosystems (e.g., mangroves, salt marshes, seagrass meadows, and macroalgae) have emerged as critical natural carbon sinks. Yet, persistent methodological inconsistencies and geographic biases hinder their reliable incorporation into blue carbon management and climate prediction. Here, we synthesize current understanding of source-sink characteristics, drivers, and formation mechanisms of coastal blue carbon ecosystems, focusing on carbon storage capacity, sequestration pathways, and spatial heterogeneity across ecosystem types. We emphasize biogeochemical processes, including sedimentation, tidal dynamics, and microbial mediation, and critically examine anthropogenic disturbances—coastal development, land-use change, pollution, and ecosystem degradation—on blue carbon dynamics. Finally, we identify critical knowledge gaps, particularly the quantification of lateral carbon fluxes and microbial carbon stabilization mechanisms, highlighting the need for integrated, multi-scale monitoring to better assess the climate mitigation potential of coastal blue carbon ecosystems.

An Innovative Multi-Model Ensemble Strategy for Subgrade Compaction Quality Assessment Incorporating Moisture Content Effects and Underlying Soil Layer Properties - Jianguang Yin; Chengzhi Xiao; Xinzhuang Cui; Huaxin Han; Luqiang Ding; Hancheng Dan (Transportation Geotechnics, 2026)

Thickness variation of black soil on sloping farmland in northeast China from 1963 to 2023 - Chang Liu; Gang Liu; Chenxi Dan; Enshuai Shen; Ya Liu; Qiong Zhang; Han Luo; Chutian Zhang; Zhen Guo; Kaishan Song (Soil and Tillage Research, 2026)

Effect and mechanism of prophage lysogeny on antimicrobial resistance and virulence of Staphylococcus aureus from retail meat - Wenyuan Zhou; Wenjuan Li; Yeling Han; Aiping Deng; Yajie Li; Lei Yuan; Dan Xiong; Guoqiang Zhu; Zhenquan Yang (Food Research International, 2026)

Dehydroepiandrosterone activates ADGRG2 to regulate chloride homeostasis and sperm motility via Gs-cAMP pathways - Dan Jiang; Ji-Fei Han; Xian-Zheng Guo; Yu-Qi Ping; Fan Yang; Peng Xiao; Jin-Peng Sun; Xiao Yu; Zhao Yang; Hui Lin (Science China Life Sciences, 2026)

Isolation and characterization of a novel strain of Rhizopus arrhizus for effective biodegradation and detoxification of zearalenone - Dan He; Yunfan Shan; Han Qiu; Gang Wang; Junqiang Hu; Yuzhuo Wu; Keke Ji; Hao Xu; Yin-Won Lee; Jianhong Xu; Xin Yan (World Journal of Microbiology and Biotechnology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Effect of the combination of lactic acid, ε-poly-L-lysine and sodium isoascorbate on the swelling, microbiomics variation, and quality attributes of vacuum-packed fresh cut lotus root - Jiahui Jiang; Qianlong Shi; Dan Li; Qingmin Chen; Cong Han; Jing Wei; Maorun Fu; Huaimei Cao; Xiaofei Xin (Postharvest Biology and Technology, 2026)

Effects of soil erosion-deposition rate and mollic epipedon thickness on sloping farmland soil nutrients in the Mollisol region of Northeast China - Chang LIU; Gang LIU; Qiong ZHANG; Chenxi DAN; Yuqian HAN; Enshuai SHEN; Zhen GUO (Pedosphere, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Biodegradable microplastics-induced free-living nitrogen fixation enhancement and diazotrophic community differentiation in soils - Yujuan Han; Peixin Gao; Jiping Song; Yanning Li; Xiao Wang; Ning Yang; Xu Zhao; Bo Liu; Chuankun Zhang; Ran Li; Dan Wen; Ying Teng (Journal of Environmental Management, 2026)

Spatiotemporal patterns, human health risks, and driving mechanisms of ARGs in the littoral zones of the largest shallow lake in North China - Kai Deng; Lei Wang; Aiwen Wang; Xun Han; Lining Zhao; Yulong Zhang; Dan Ma; Fei Zheng; Sijun Dong (Journal of Environmental Chemical Engineering, 2026)

Superheated steam-treated wheat flour for the preparation of low-fat short dough biscuits: Effects on dough characteristics and biscuit quality - Chang Han; Xuepan Qi; Yamei Jin; Na Yang; Dan Xu; Fengfeng Wu; Xueming Xu (Food Hydrocolloids, 2026)

AGFormer: Adaptive Spatiotemporal graph informed transformer for multi-reservoir inflow forecasting - Ming Fan; Pengfei Hu; Xiaoxue Han; Wei Zhang; Hyun Kang; Yue Ning; Dan Lu (Environmental Modelling & Software, 2026)

Genetic diversity of Theileria species identified from questing and parasitic ticks in selected areas in Qinghai, China - Yuan Han; Zhi Li; Yong Fu; Junlong Liu; Dan Jia; Chunhua Li; Hong Yin; Mengtong Lei (Veterinary Research Communications, 2026)

A Comprehensive Evaluation of the Quality Improvement of Vegetable Soybean Under Saline-alkali Stress - Sijie Xiong; Jie Dai; Dan Zhu; Haiyu Jia; Ping Zhao; Chenggang Han; Longgang Zhao (Journal of Crop Health, 2026)

Season-dependent combined effects of nitrogen deposition and precipitation change on soil microbial communities and functions in a subtropical forest - Zhiming Guo; Jianbo Fang; Jinhong He; Xiuling Ni; Yanxia Nie; Xiaoge Han; Dan He; Xiangping Tan; Weijun Shen; Anna Gunina (Biology and Fertility of Soils, 2026)

The presence of native semi-fossorial herbivores enhances the coupling between species and functional diversity in alpine meadows - Yuan Yuan Duan; Kun Qin; Yu Chen; Jie Li; Ni Wang; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Agriculture, Ecosystems & Environment, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Breaking the activity-stability trade-off in ammonia borane hydrolysis via atomically engineered platinum single atom-nickel cluster synergistic interfaces - Jiankang Zhang; Panzhe Qiao; Jinlong Hu; Xiuxiu Han; Dan Feng; Hao Xu; Xinshuo Zhao; Jun Zhong; Yongxiao Tuo; Yong Qin; Chaohe Xu (Science Bulletin, 2026)

Effects of season, temperature, and humidity on feeding behavior and feed conversion ratio in multiple sheep breeds monitored via an automated electronic feeding system - Guoxing Jia; Weimin Wang; Huibing Tian; Xiaojuan Wang; Yuan Zhao; Yukun Zhang; Kunchao Han; Xioabing Yang; Dan Xu; Tong Cai; Shiyu Zhao; Hongmei Hou; et al. (Small Ruminant Research, 2026)

Unveiling the binding mechanism between egg white proteins and wheat glutens during the dough mixing process - Dan Zhang; Peichuang Li; Shan Li; Haiyuan Zhou; Han Tao; Wan-Hao Cai (Food Hydrocolloids, 2026)

Interaction mechanism between two stages of separation explains residual rice husk formation in a multi-baffle separation duct - Shouyu Ji; Xianle Li; Dan Zhao; Hao Li; Ze Sun; Zhuozhuang Li; Anqi Li; Haonan Gao; Xinlei Wang; Yanlong Han; Fuguo Jia (Food and Bioproducts Processing, 2026)

Bio-organic fertilization promotes soil nutrient cycling and reduces CO2 emissions via regulating bacterial communities in vegetable production system - Lijun Ren; Lili Dong; Yanyu Han; Jiaqi Li; Qingfeng Fan; Dan Wei; Hongtao Zou; Yulong Zhang (European Journal of Soil Biology, 2026)

Spatially isolated single-site VOx on activated carbon for efficient oxidation of carbohydrates to formic acid - Zhen Zhang; Xiaojian Tian; Yuxiao Sun; Dandan Han; Bang Gu; Dan Wu; Armin Rezayan; Xian Wu; Jingpeng Zhao; Jianshe Wang; Tianliang Lu; Renfeng Nie; et al. (Chemical Engineering Journal, 2026)

Runoff hydrodynamic variations on terraced slopes with different soil types in the dry–hot valley region, Southwest China - Dan Yang; Donghong Xiong; Shasha Han; Baojun Zhang; Qihua Liao; Linpeng Wu (CATENA, 2026)

Gentianine inhibits colorectal cancer growth via HIF1α/SLC7A11-modulated ferroptosis through suppression of METTL3-mediated AKT2 m6A methylation - Lili Han; Shuman Li; Dan Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Predicting macrolide resistance in pediatric Mycoplasma pneumoniae pneumonia: A machine learning modeling study - Shuo Yang; Xinying Liu; Huizhe Wang; Yaowei Han; Dan Sun; Huanmin Li; Liting Ma; Haokai Wang; Xinmin Li (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Effects of water quality and hydrologic factors on fish diversity in subtropical urban river ecosystems - Qiaoyu Cui; Fangbo Qiu; Chao Li; Yiang Wang; Dan Han; Yan Huang (Environmental Biology of Fishes, 2026)

A review of synergistic strategies for photothermal catalytic VOCs degradation: Catalyst design and reaction system optimization - Dan Zhang; Tao Han; Fahui Wang; Xinxin Han; Shuxian Yin; Fang Liu; Ziyi Jing; Guanyi Chen (Journal of Environmental Chemical Engineering, 2026)

Multifunctional biomimetic nanoparticles for rheumatoid arthritis via binary inhibiting macrophage glycolysis and proinflammatory cytokine - Han Yang; Guanxin Zhao; Min Liu; XiaoFang Li; Siyi Liu; Jingwen Jia; Jingya Xiu; Dan Li; Jiulong Zhang; Xiuli Zhao (Chemical Engineering Journal, 2026)

Hydrogen bond driven deep eutectic solvent strategy for enhanced sludge dewatering via protein network remodeling - Lichong Duan; Shuyue Han; Zhiwen Zhang; Jiazhen Xu; Dan Wang; Shuang Chen; Jiqin Wang; Jinghua Lv; Chao Guo; Yunbei Li (Bioresource Technology, 2026)

Whole-grain black rice diet rewires the single-cell transcriptomic landscape of age-related ovarian decline in mice - Yi-Xuan Tu; Dan-Yang Wang; Jun Ma; Ke-Chun Yu; Sheng-Hui Li; Bo-Han Li; Xin-Yin Deng; Shan Li; Hong-Kai Wang; Tailang Yin; Ling Wang; Zhen-Xia Chen (Science China Life Sciences, 2026)

Dynamic health risk assessment of chromium exposure in soil and groundwater at tannery sites: a Bayesian network perspective - Shan-shan Guo; Yu Wang; Yong qiang Tian; Hao Wu; Yang Li; Xiao dan Jin; Xin Li; Ze-lin Zhou; Han Zhang; Jin-yan Yang (Environmental Geochemistry and Health, 2026)

An mRNA vaccine expressing the capsid protein of goose astrovirus elicits protective immunity - Dongmin Zhao; Xinmei Huang; Lijiao Zhang; Kaikai Han; Jing Yang; Fengying Lu; Fengyao Wu; Xin Yin; Dan Su; Kai Xu; Yin Li; Xiaofei Zhang; et al. (Veterinary Microbiology, 2026)

The novel_miR-123 targets SeFas4 to inhibit lipogenesis of Spodoptera exigua post Bacillus thuringiensis GS57 infection - Bo Gao; Yujie Ji; Dan Zhao; Han Wu; Lu Zhang; Yitong Yan; Yifan Xie; Qiuyu Shi; Qian Wang; Wei Guo (Pesticide Biochemistry and Physiology, 2026)

Starch/polyvinyl alcohol based smart packaging reinforced with recycled pitaya peel-derived anthocyanins for dual-function pork freshness monitoring and shelf-life extension - Lili Ma; Wenyu Han; Yurou Jiang; Zhenquan Yang; Dan Xiong; Shuo Wang; Wenyuan Zhou; Xin-an Jiao; Lei Yuan (Meat Science, 2026)

The effects of prenatal GenX (HFPO-DA) exposure on gut microbiota and metabolic function in pregnant rats and their offspring - Wenchao Han; Xinpeng Zhang; Dan Li; Wendong Liu; Yanxia He; Haitao Shang; Zhugen Yang; Hongyun Liu; Wenjing Zhu (Environmental Pollution, 2026)

Developing a bioprocess for a novel trehalose tetraester biosurfactant from Rhodococcus erythropolis KB1 and evaluating its efficacy in PAH bioremediation - Ning Zhu; Changze Han; Xiaopeng Guo; Dan Luo; Feifan Leng; Yan Zhuang; Pengfei Gao; Peijie Zhao; Kai Zhou; Jixiang Chen; Yonggang Wang (Bioresource Technology, 2026)

The Dual Roles of Microglia- and Astrocyte-Derived Exosomes in Cerebral Ischemia–Reperfusion Injury: from Intercellular Communication to Therapeutic Prospects - Zhengyuhan Yang; Huilin Chen; Zhenwang Zhang; Xiaoming Wei; Wanting Han; Tie Peng; Dan Zhu; Chao Liu (Molecular Neurobiology, 2026)

Comparison of soil enzyme activity and stoichiometry between urban park and forest in the Pearl River Delta region, China - Han Sheng; Xu Li; Luis Carlos Ramos Aguila; Fasih Ullah Haider; Shu-Yi-Dan Zhou; Guopeng Wu; Chushu Meng; Yunxuan Deng; Juxiu Liu (Applied Soil Ecology, 2026)

Systematic Review and Meta-Analysis on Heavy Metals and Trace Elements in Mild Cognitive Impairment - Yaxin Dong; Lu Ren; TianRan Tang; Xinyi Zhang; Dan Han; Yingyi Luo; Liqiang Wang; Zonghui Cui; Sheng Ji; Jianheng Zheng; Ying Qing (Biological Trace Element Research, 2025)

Taxonomy and phylogeny of Erysiphe species on Liquidambar formosana (Hamamelidaceae) - Jing Feng; Shuang-Bao Wang; Shu-Yan Liu; Michael Bradshaw; Uwe Braun; Shou-Rong Yu; Guan-Xiu Guan; Dan-Ni Jin; Zhao-Yang Zhang; Han-Xing Gao (New Zealand Journal of Botany, 2025)

Spirocyclic polyketide analogues from the endophyte fungus Penicillium sp. YUD25002 associated with Panax notoginseng - Wen-Jing Wang; Ju-Cheng Zhang; Yan Geng; Hai-Xia Dong; Fei Xie; Tian-Peng Xie; Zhi-Feng Zi; Dan-Dan Xia; Han-Jue Zhang; Hao Zhou; Min Yin; Zhong-Tao Ding (Phytochemistry Letters, 2025)

Thrust enhancement of cycloidal propellers by using flaps to compensate for the virtual camber effect - Han Yan; Tianwen Liu; Tongfu Zou; Dan Xia (Ocean Engineering, 2025)

Dynamic performance of trains in submerged floating tunnels under wave loading - Linzhong Han; Bo Huang; Wenlong Luo; Cheng Cui; Jie Hou; Hao Ding; Ke Li; Liang Cheng; Dan Zhong; Jiawei Zhou (Ocean Engineering, 2025)

The study of stiffness design of tube, cable, and joint in submerged floating tunnel by segmentation analysis method under static and dynamic loads - Jie Hou; Bo Huang; Linzhong Han; Peng Chen; Hao Ding; Jianting Zhou; Ke Li; Liang Cheng; Dan Zhong; Jiawei Zhou (Ocean Engineering, 2025)

Soil organic carbon decline under bamboo invasion: The role of microbial carbon cycling - Chushu Meng; Chaotang Lei; Xu Li; Han Sheng; Guopeng Wu; Juxiu Liu; Shu-Yi-Dan Zhou (Journal of Environmental Management, 2025)

Preparation of CrMnTi catalysts and mechanistic study on their photothermal synergistic degradation of toluene - Dan Zhang; Ziyi Jing; Li'an Hou; Fahui Wang; Anchao Zhang; Yonghui Li; Shuxian Yin; Tao Han (Journal of Environmental Chemical Engineering, 2025)

Superheated steam-treated wheat flour: A novel approach to improve freeze-thaw stability of frozen raw noodles - Xuepan Qi; Chang Han; Ying Wang; Yamei Jin; Dan Xu; Fengfeng Wu; Xueming Xu (Innovative Food Science & Emerging Technologies, 2025)

Functional characterization of two Caspase-1 transcripts that associated with ASC and NLRC3 in apoptosis and inflammatory response in large yellow croaker Larimichthys crocea - Qiu Yu Hu; Kun Huang Han; Qiu Ye Huang; Wen Feng Cui; Qiao Yun Yang; Yi Dan Liu; Shang Qi Zhao; Xian Yuan Zeng; Ying Li; Wen Qi Zha; Yi Lei Wang; Yong Hua Jiang; et al. (Fish & Shellfish Immunology, 2025)

Facilitating H-spillover on Ni-ν0 paired sites via CO2-assisted H2 reduction engineering of Ni-CeO2 catalyst to accelerate CO2 methanation - Kangyu Han; Jie Ren; Yao Lu; Zixu Ma; Dongsheng Zhang; Aizhong Jia; Hualiang An; Peng Zhai; Meiya Yang; Dan Guo; Yanji Wang (Chemical Engineering Journal, 2025)

Construction of multifunctional biomimetic nanocarriers for the treatment of atherosclerosis via precise cholesterol removal and ROS scavenging - Xiaofang Li; Min Liu; Jingwen Jia; Han Yang; Guanxin Zhao; Siyi Liu; Jingya Xiu; Dan Li; Jiulong Zhang; Xiuli Zhao (Chemical Engineering Journal, 2025)

Chitosan-derived nanoemulsion enriched with Streptomyces metabolites for target control of tobacco leaf spot, enhanced foliar retention and plant nutrition - Xue Han; Chunli Xu; Rui Yang; Dan Chen; Yaning Li; Beibei Ge (Chemical Engineering Journal, 2025)

Identification of Biomarkers Related to the Pathogenesis and Prognosis of Pediatric Moyamoya Disease Via Cerebrospinal Fluid Proteomics - Youngbo Shim; Seung Ah Choi; Kisoon Dan; Eun Jung Koh; Saehim Ha; Ji Hoon Phi; Joo Whan Kim; Dohyun Han; Seung-Ki Kim (Translational Stroke Research, 2025)

Genetic association between SKA2 rs7208505 and preterm birth in Korean women - Eun Jo Lee; Sung Ho Han; Yun Dan Kang; Jong Soo Kim; Jin Wan Park; Han Jun Jin (Molecular Biology Reports, 2025)

Endomycorrhizal fungi improve soil nitrogen transformation rates and nitrogen uptake rates of nitrate-preferring plant - Chang Zhao; Shenyan Dai; Shending Chen; Chanjuan Hu; Xiaoqian Dan; Xiaoxiang He; Jun Zhao; Han Meng; Zucong Cai; Jinbo Zhang (Journal of Soils and Sediments, 2025)

Effect of straw-based vertical drains on consolidation of dredged sediment under intermittent vacuum preloading - Junjun Ni; Shusen Liu; Mengying Gao; Qiyuan Han; Jiaxing Weng; Dan Zhang (Journal of Soils and Sediments, 2025)

Characterisation and diagnostic model of monogenic lupus - Mengyang Yang; Dan Lu; Yulu Li; Xiongbin Chen; Han Yang; Wenxiu Mo; Huawei Mao (Immunologic Research, 2025)

Assessment of habitat characteristics in typical seagrass bed ecosystems along the coast of Changhai County, Dalian - Yuchen Chu; Jun Yang; Juncheng Yin; Jie Tian; Jun Song; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; Yanjun Wang; Qian Sun; Quanxiang Meng; et al. (Acta Oceanologica Sinica, 2025)

Effect of Moisture Content on the Evaluation of Subgrade Compaction Quality using Intelligent Compaction Measurement Values - Jianguang Yin; Chengzhi Xiao; Huaxin Han; Luqiang Ding; Xinzhuang Cui; Hancheng Dan (Transportation Geotechnics, 2025)

Reply to “Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China” - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Analysis of APOD and FABP7 genes polymorphisms and their association with feed efficiency in Hu sheep - Ziyue Xiao; Deyin Zhang; YuKun Zhang; Dan Xu; Zongwu Ma; Kunchao Han; Lijuan He; Chengqi Yan; Qi Zhang; Lianjun Feng; Mengru Pu; Lei Gao; et al. (Small Ruminant Research, 2025)

Ecological restoration in plateau pika-disturbed alpine meadows: Soil-microbe-enzyme stoichiometry and microbial adaptations during vegetation recovery of bare patches - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Journal of Environmental Management, 2025)

Highly conductive GaN-Cu3(HITP)2/PANI gas sensor based on GaN double heterojunction coupled with deep learning for accurate trimethylamine mixed gas detection - Dan Han; Lianao Yan; Yu Wang; Yuru Pang; Zhekai Zhang; Xiuli He; Guojing Wang; Weidong Wang; Shengbo Sang (Chemical Engineering Journal, 2025)

Metal-organic frameworks based solid-state electrolytes for high-performance lithium metal batteries - Zhenjie Dai; Yuyu Su; Dan Liu; Qi Han; Tamar L. Greaves; Weiwei Lei; Zongjian Liu; Zhengfei Chen (Chemical Engineering Journal, 2025)

Regulation of electronic structure and enhancement of potassium storage performance in NbSSe nanosheets facilitated by intermolecular heterojunctions - Han Xu; Xin Du; Zhanxiao Lu; Jiafan He; Luxiang Wang; Dan Li (Chemical Engineering Journal, 2025)

Effects of plateau pika disturbance on soil net nitrogen mineralization from small to large scales in alpine meadows - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (CATENA, 2025)

Expression of LGALS3 and XPNPEP2 genes and their association with growth traits in sheep - Guoxing Jia; Weimin Wang; Huibing Tian; Xiaojuan Wang; Yukun Zhang; Yuan Zhao; Lijuan He; Zongwu Ma; Xioabing Yang; Dan Xu; Kunchao Han; Peiliang Cao; et al. (Tropical Animal Health and Production, 2025)

Oxygenated aromatic compounds as dominant contributors to the oxidative potential of PM2.5 emitted from biomass burning and coal combustion - Feiyan Cao; Xinxin Feng; Yingjun Chen; Hongxing Jiang; Yong Han; Tian Chen; Yu Shang; Dan Li; Qianyu Zhang; Huimin Ma; Jun Li; Gan Zhang (Journal of Hazardous Materials, 2025)

Genesis of high hexavalent chromium groundwater in shallow aquifers from typical irrigation districts of northwest China - Han Lu; Peiyue Li; Dan Wang; Jing Ning; Fei Xu; Misbah Fida (Journal of Hazardous Materials, 2025)

Laccase-mimicking chiral Cu-nanozymes for enantioselective catalysis of phenolic substrates - Qiaodan Du; Zhihao Mu; Dan Liang; Xinman Han; Yuan Zhao; Wei Ma (Journal of Hazardous Materials, 2025)

CTAB-Assisted, controlled preparation of a CeZrOx/CuSAPO-34 catalyst and its performance for the synergistic removal of NOx and toluene from flue gas - Qian Zhou; Xuehui Jia; Rong Liu; Fangfei Liu; Han Zhang; Dan Hou; Lu Wang; Yunkuo Luo; Bichun Huang; Hong Huang; Xia Gong; Chenglong Yu (Journal of Environmental Chemical Engineering, 2025)

Reaction calorimetry and structural crystal properties of non-ideal binary rhabdophane solid solutions (Ce1−xREExPO4·nH2O) - Alexander P. Gysi; Nicole C. Hurtig; Hannah Juan Han; Emma C. Kindall; Xiaofeng Guo; Dmitrii A. Kulik; George Dan Miron (Geochimica et Cosmochimica Acta, 2025)

Bread-inspired rapid gelation-induced bubble “growth-fixation” strategy to fabricate macroporous hydrogels for flexible sensors - Yu Jiang; Yixiang Chen; Wanqi Feng; Xun Zhang; Siqi Zhang; Xin Zhong; Yashu Han; Dan Yu; Wei Wang (Chemical Engineering Journal, 2025)

Isolation and characterization of minor monoterpene glycosides from the roots of Paeonia lactiflora - Yongliang Ding; Dan Han; Qian Tang; Lijuan Wang; Zhongtang Qu (Biochemical Systematics and Ecology, 2025)

Numerical study on the influence mechanism of feed rate on separation quality in a multi-baffle separation duct - Shouyu Ji; Anqi Li; Yanlong Han; Hao Li; Ze Sun; Dan Zhao; Haonan Gao (Biosystems Engineering, 2025)

Effect of paddy grain flow behaviour on orientation adjustment mechanisms in rubber roll huller feeding chute - Hao Li; Yanlong Han; Dan Zhao; Jincheng Zhang; Anqi Li; Ze Sun; Shouyu Ji; Haonan Gao (Biosystems Engineering, 2025)

Prevalence and related factors of antenatal depression in 11 provinces and cities of China: a 100,000 population-based study - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Midgut microorganisms transformed into hemolymph pathogens: Mediating DUOX-ROS immune response to regulate the insecticidal activity of Bacillus thuringiensis against Spodoptera exigua - Yujie Ji; Bo Gao; Dan Zhao; Lu Zhang; Han Wu; Yifan Xie; Qiuyu Shi; Wei Guo (Pesticide Biochemistry and Physiology, 2025)

Phthalate-related metabolites from an endophytic Alternaria sp. YUD24001 associated with Aconitum hemsleyanum - Fei Xie; Zhi-Feng Zi; Wen-Jing Wang; Dan-Dan Xia; Yan Geng; Si-Jie Xie; Han-Jue Zhang; Hao Zhou; Zhong-Tao Ding (Phytochemistry, 2025)

Predicting arsenic bioaccessibility: A global data-driven machine learning approach and its implication for reducing carbon emissions - Haonan Zhang; Dan Han; Maosheng Zhong; Tianxiang Xia; Suo Yang; Shijie Wang; Ping Zhang; Lin Jiang (Journal of Hazardous Materials, 2025)

Children’s home environments as reservoirs of antimicrobial resistance: Divergent urban-rural risks from antibiotic resistance genes and pathogens - Shuang Du; Hao Tang; Zhang Wang; Han Chen; Xinyi Fang; Jin Sun; Zhiping Niu; Yiwei Liu; Yuanzhuo Hu; Wen Su; Zhenhua Zhang; Tippawan Prapamontol; et al. (Journal of Hazardous Materials, 2025)

Bimetallic Mn and Cr co-doped nickel cobalt phosphide nanoneedle arrays as bifunctional electro catalysts for overall water splitting - Yongyi Zhang; Mingyan Zhang; Haochen Zhang; Dan Han; Jinping Wang; Rui Yang; Chunling Zuo; Xiaoshuang Chen (Fuel, 2025)

Simultaneous determination of pesticide residues and rapid discrimination of corn production origin using ambient ionization mass spectrometry combined with machine learning - Hang Su; Lifeng Han; Miaoxiu Ge; Xiangyu Wang; Hongping Zeng; Dan Zhao; Wei Xiong; Luhong Wen (Food Chemistry, 2025)

6,7-Dimethoxy-3H-Quinazolin-4-One as a dual-function inhibitor of polyphenol oxidase and bacteria: biological evaluation, mode of action, and anti-browning studies - Xiu-Zhen Li; Jin-Rui Qiao; Yi-Rui Wu; Dong-Yan Zhou; Yu-Dan Shi; Shu-Meng Zhu; Qiu-Han Bai; Xiao-Lei Xia; Wei-Ming Chai (Food Bioscience, 2025)

Different benefit from clonal integration of stress signal between a stoloniferous alien invasive plant and its congeneric native one - Jie Deng; Jiao Tian; Cheng-Gang Qiu; Xue-Mei Wang; Jie Jiang; Han-Jun Yang; Yi Dan; Chang-Fan Chen; Su-Juan Duan; Jin-Song Chen (Flora, 2025)

Corrigendum to “Different benefit from clonal integration of stress signal between a stoloniferous alien invasive plantand its congeneric native one” [FLORA Volume 326, May 2025, 152724] - Jie Deng; Jiao Tian; Cheng-Gang Qiu; Xue-Mei Wang; Jie Jiang; Han-Jun Yang; Yi Dan; Chang-Fan Chen; Su-Juan Duan; Jin-Song Chen (Flora, 2025)

Adaptive fertilization strategies for premature senescence challenges in film-mulched maize: Insights from a 4-year field study - Haixiang Xiong; Chi Ma; Shujie Sun; Ziyi Wang; Ji Zhao; Chun Zhang; Lin Yang; Zhaoyun Dong; Zhikuan Jia; Dan Liu; Qingfang Han; Xudong Zhang (European Journal of Agronomy, 2025)

Construction and optimization of low carbon-to-nitrogen ratio-adapted Chlorococcum-Bacteria symbiosis for energy-efficient wastewater remediation - Ru Yan; Han Ji; Zhuo-Chao Liu; Mei-Qi Ren; Shuai Wang; Li-Ming Yang; Dan Cui (Bioresource Technology, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

A nature-inspired metal-free electrocatalyst towards efficient electron transfer and robust cascade oxygen reduction for wastewater treatment - Yao Pan; Xudong Yang; Zhe Wang; Yu Han; Junxi Guo; Ran Yin; Shanyuan Niu; Dan Shan; Lili Ding; Jinfeng Wang; Hongqiang Ren (Water Research, 2025)

The adsorption capacity and genetic mechanism analysis of Yarrowia phangngaensis for multiple heavy metals - Wenqi Xiao; Shuyi Chen; Maojie Zhao; Dan Wen; Lianxin Peng; Liang Zou; Jialiang Han; Qiang Li (Journal of Hazardous Materials, 2025)

Machine learning based prediction by PlantCdMiner and experimental validation of cadmium-responsive genes in plants - Chaoqun Xu; Ling Sun; Lu-Dan Zhang; Ze-Jun Guo; Ji-Cheng Wang; Li-Han Zhuang; Dong-Na Ma; Ling-Yu Song; Jing Li; Qian-Su Ding; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2025)

Dietary vitamin C improves muscle hardness and springiness associated with collagen and elastin synthesis in grass carp (Ctenopharyngodon idella) - Xin-Lei Xue; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Yang Liu; Yao-Bin Ma; Jun Jiang; Dong Han; Wen-Bin Zhang; Wei-Dan Jiang (Food Research International, 2025)

Experimental investigation on the interface of concrete-filled steel tubular (CFST) structures based on roughness and geometric deviation - Dan-Yang Ma; Ying-Qian Guo; Lin-Hai Han; Chuan-Chuan Hou (Engineering Structures, 2025)

High-quality reference genome and population analysis of allotetraploid Elymus sibiricus provide insight into genome origin and environmental adaptations to the Qinghai-Tibetan Plateau - Xinrui Li; Changbing Zhang; Lili Wang; Gai Huang; Daxu Li; Changmian Ji; Zujun Yang; Minghong You; Lijun Yan; Lili Chen; Wenlong Gou; Xiong Lei; et al. (Science China Life Sciences, 2025)

Insights into the changes in cell wall polysaccharides and ROS metabolism of fresh-cut chili pepper (Capsicum annuum L.) infected by Enterobacter cloacae - Zudi Li; Xiaoyan Zhao; Dan Wang; Pan Wang; Shuang Zhao; Hangjun Chen; Yanchao Han; Wenting Zhao (Postharvest Biology and Technology, 2025)

Using the windmill-shaped array layout to realize the self-rolling propulsion of a multi-tentacled underwater robot - Zhihan Li; Ming Lei; Songlong Jiao; Han Yan; Yuyao Li; Dan Xia (Ocean Engineering, 2025)

Identifying hydrogeochemistry evolution mechanism in high-sulfur non-ferrous metal mining areas via hydrochemical characteristics and isotopic evidence - Bing Wang; Lei Ma; Jia-zhong Qian; Yun-hai Fang; Wei Xie; Dan Ding; Huan Zhou; Yang Long; Han-ying Shen; Qiang Yang (Journal of Contaminant Hydrology, 2025)

A Rock Strength Prediction Model Utilizing Real-Time Data from Percussion–Rotary Drilling Measurements - Guo-Hua Zhang; Jia-Cheng Yu; Zhao-Yang Han; Sheng-Lian Li; Lu-Zhao Dan; Dong-Jie Hua; Feng Xiong; Yu-Yong Jiao (Rock Mechanics and Rock Engineering, 2025)

Fibrinogen-tau Aggregates Exacerbate Tau Pathology and Memory Deficits in Alzheimer’s Disease Model Mice - Tingting Wen; Lanxia Meng; Han Liu; Qian Zhang; Lijun Dai; Liqin Huang; Liang Dan; Kedong Zhu; Jiaying Luo; Zhaohui Zhang (Neuroscience Bulletin, 2025)

Microbially mediated mechanisms underlie N2O mitigation by bio-organic fertilizer in greenhouse vegetable production system - Lijun Ren; Lili Dong; Guopeng Liang; Yanyu Han; Jiaqi Li; Qingfeng Fan; Dan Wei; Hongtao Zou; Yulong Zhang (Applied Soil Ecology, 2025)

Increased frequency and severity of global compound dry and heat wave events in a daily scale - Lijun Jiang; Jiahua Zhang; Linyan Bai; Jiaqi Han; Xianglei Meng; Dan Cao; Ali Salem Al-Sakkaf (Journal of Hydrology, 2025)

Self-assembled materials from MXene and polyoxometalates based on polymerization of dopamine in one step for non-radical dominated degradation of sulfamethoxazole - Zushen Xu; Hua Jiang; Yongwei Han; Dan Zhang; Zhong Sun; Xixin Duan (Journal of Environmental Management, 2025)

Overall quality changes of fresh-cut cowpeas (Vigna unguiculata L. Walp.) during storage: Correlation of packaging materials and quality - Wen Zhang; Mengtong Han; Yubin Wang; Zhiwen Ge; Wanfu Hou; Liqun Zhao; Xiaoyan Zhao; Dan Wang (Food Chemistry, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

Ultra-low Pt induced amorphous/crystalline heterophase Pt-Co2P hollow nanotubes for superior water electrolysis at industrial temperatures - Ziting Li; Peng Zhou; Mingyan Zhang; Haochen Zhang; Yongyi Zhang; Dan Han; Xiaoshuang Chen (Fuel, 2025)

Different benefit from clonal integration of stress signal between a stoloniferous alien invasive plantand its congeneric native one - Jie Deng; Jiao Tian; Cheng-Gang Qiu; Xue-Mei Wang; Jie Jiang; Han-Jun Yang; Yi Dan; Chang-Fan Chen; Su-Juan Duan; Jin-Song Chen (Flora, 2025)

A Novel Model of Traumatic Optic Neuropathy Under Direct Vision Through the Anterior Orbital Approach in Non-human Primates - Zhi-Qiang Xiao; Xiu Han; Xin Ren; Zeng-Qiang Wang; Si-Qi Chen; Qiao-Feng Zhu; Hai-Yang Cheng; Yin-Tian Li; Dan Liang; Xuan-Wei Liang; Ying Xu; Hui Yang (Neuroscience Bulletin, 2025)

The dual-effect of the CO2 capture efficient by red mud under atmospheric pressure and synergistic de–alkalization - Yuhao Fan; Junsong Bao; Huan Yang; Xinyu Lou; Dan Chen; Yuanfa Zhuang; Jiali Han; Lei Hou; Jun Jin; Tan Chen (Clean Technologies and Environmental Policy, 2025)

Capsular Polysaccharides Are Crucial for the Biosorption of Aqueous Pb(II) Ions by Limosilactobacillus fermentum B44 In Vitro - Wenhui Yu; Yitian Wang; Jin Han; Dan Hu; Chenbing Zhao; Zhenmin Liu; Zhengjun Wu (Biological Trace Element Research, 2025)

Mechanism of rice bran removal at individual grain and population levels in abrasive rice mill - Ze Sun; Xinlei Wang; Anqi Li; Jiaming Fei; Wenyu Feng; Dan Zhao; Yanlong Han; Fuguo Jia; Hao Li; Shouyu Ji; Zhuozhuang Li (Biosystems Engineering, 2025)

Water quality parameters-based prediction of dissolved oxygen in estuaries using advanced explainable ensemble machine learning - Xingda Chen; Chenyao Zhao; Jinyue Chen; Hao Jiang; Dan Li; Jing Zhang; Bo Han; Shuisen Chen; Chongyang Wang (Journal of Environmental Management, 2025)

Pickering emulsion stabilized by egg derived reconstituted lipid nanoparticles for encapsulation and oral delivery of curcumin - Dan Han; Lihua Ji; Mingzhou Lu; Dingran Li; Xiangling Sheng; Jiaxing Zhang; Cheng Wang (Food Chemistry, 2025)

Nomogram for Predicting Long-term Outcomes of Encephaloduroarteriosynangiosis in Toddlers with Moyamoya Disease: a Longitudinal and Cross-sectional Study - Qingbao Guo; Yan-Na Fan; Qian-Nan Wang; Jingjie Li; Cong Han; Zhengxing Zou; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; et al. (Translational Stroke Research, 2025)

Microrna363-5p targets thrombospondin3 to regulate pathological cardiac remodeling - Yu-kun Ma; Xin-yi Han; Shu-huai Zan; Hui-ting Liu; Xue-yan Zhou; Dan-xue Zhao; Rui Xing; Peng Zhao (Molecular and Cellular Biochemistry, 2025)

Safety profiles of fondaparinux in pregnant women: a systematic review and meta-analysis - Dan Shan; Jinbiao Han; Yurou Ji; Yuexiao Wu; Ke Yi (European Journal of Clinical Pharmacology, 2025)

Groundwater health risks and water quality assessment in the sources of many mighty rivers in Asia: Ngari, Tibet - Fei He; Shehong Li; Lian Song; Qiao Han; Dan Zeng Ya Jie; Yong Shui; Jen-How Huang (Process Safety and Environmental Protection, 2025)

The role of 20-hydroxyecdysone and juvenile hormone in insecticidal activity of Bacillus thuringiensis regulated by DUOX-ROS immunity in Spodoptera exigua - Yujie Ji; Bo Gao; Dan Zhao; Lu Zhang; Han Wu; Yifan Xie; Qiuyu Shi; Yao Wang; Wei Guo (Pesticide Biochemistry and Physiology, 2025)

Favorable climate conditions for rice cultivation existed 5000 years ago in the semi-arid Loess Plateau of China - Dan Zhang; Xiujia Huan; Yajie Dong; Xiaoning Zhang; Qiang Zhang; Lupeng Yu; Jianye Han; Xiaoyan Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Degradation of myosmine by a novel bacterial strain Sphingopyxis sp. J-6 and its degradation pathways - Bingjun Dang; Hui Gao; Wei Jia; Yuwei Zhang; Zicheng Xu; Dan Han; Jinchu Yang; Yao Huang; Zheng Chen; Yadi Wang; Yingqiu Duan; Ruohua Yuan; et al. (Journal of Hazardous Materials, 2025)

A method for improving milling quality based on pre-milling in the combined rice milling process - Ze Sun; Anqi Li; Shouyu Ji; Hao Li; Zhuozhuang Li; Haonan Gao; Xinlei Wang; Xianle Li; Yanlong Han; Dan Zhao (Innovative Food Science & Emerging Technologies, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Isolation and detection strategies for decoding the heterogeneity of extracellular vesicles - Shi-Ming Wang; Dan Wang; Yu-Qing Shen; Mo-Han Wang; Fei Jia; Zhao Pan; Liang Dong; Xian-Yu Zheng; Hui-Qin Wen; Rui Xu (Chemical Engineering Journal, 2025)

Vagus nerve stimulation (VNS) preventing postoperative cognitive dysfunction (POCD): two potential mechanisms in cognitive function - Zi-Feng Xie; Sheng-Yu Wang; Yuan Gao; Yi-Dan Zhang; Ya-Nan Han; Jin Huang; Mei-Na Gao; Chun-Guang Wang (Molecular and Cellular Biochemistry, 2025)

The ratio of transpiration to evapotranspiration dominates ecosystem water use efficiency response to drought - Shanshan Yang; Jiahua Zhang; Jiaqi Han; Yun Bai; Lan Xun; Sha Zhang; Dan Cao; Jingwen Wang (Agricultural and Forest Meteorology, 2025)

Fe2+ inhibits spring viraemia of carp virus proliferation via ATG14-dependent autophagy - Zhuo-Cong Li; Can Zhang; Na Xu; Xiao Xu; Ke-Jia Han; Chu-Jing Zhou; Yang-Yang Wang; Bao-Jie Cui; Dan-Dan Chen; Long-Feng Lu; Shun Li (Aquaculture, 2025)

Cadmium induces spontaneous abortion by impairing endometrial stromal cell decidualization - Xue-Ke Zhang; Xuan Li; Xing-Xing Han; Dong-Ying Sun; Yu-Qin Wang; Zi-Zhuo Cao; Lu Liu; Zi-Han Meng; Guo-Jing Li; Yu-Jie Dong; Dan-Yang Li; Xiao-Qing Peng; et al. (Toxicology, 2025)

Hidden Archaean basement beneath the southwestern Yangtze Craton: Evidence from 2.8 Ga xenocrystic zircons in an early Cretaceous dolerite dyke - Yangguang Han; Liang Qiu; Dan-Ping Yan; Ping Xu; Minglong Li; Weihua Sun; Junting Qiu; Wei Yang (Journal of Asian Earth Sciences, 2025)

Fabrication and characterization of lysozyme fibrils/Zein complexes for resveratrol encapsulation: Improving stability, antioxidant and antibacterial activities - Min Huang; Yuling Song; Han Wang; Hao Li; Rongmi Zhou; Qing Cao; Lijuan Dong; Gerui Ren; Di Wu; Qunfang Lei; Wenjun Fang; Dan Deng; et al. (Food Chemistry, 2025)

Novel glycolipids from Potentilla anserina L. rhizomes: Anti-inflammatory, hepatoprotective activities, and structure-activity relationship studies - Dan Yang; Zhihui Liu; Sikai Li; Na Han; Jianxiu Zhai; Jun Yin (Food Bioscience, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Salinity affects C/N ratio through differential responses of carbon and nitrogen metabolism in mangrove Avicennia marina leaves revealed by combined analysis of transcriptome and metabolome - Jing Li; Ling-Yu Song; Ze-Jun Guo; Chao-Qun Xu; Lu-Dan Zhang; Ji-Cheng Wang; Han-Chen Tang; Ming-Jin Dai; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2025)

SaTDT enhanced plant tolerance to NaCl stress by modulating the levels of malic acid and citric acid in cells - Xiangyu Wei; Li Xu; Suisui Dong; Nina He; Qianqian Xi; Dan Yao; Qianqian Wang; Yue Zuo; Chen Ling; Meiting Qi; Wen Bai; Kai Han; et al. (Plant Molecular Biology, 2025)

Investigating the molecular mechanism of vitexin targeting CDK1 to inhibit colon cancer cell proliferation via GEO chip data mining, computer simulation, and biological activity verification - Chenying Zhao; Yifan He; Hailong Shi; Chaojun Han; Xingmei Zhu; Chuan Wang; Bin Wang; Jiping Liu; Yongheng Shi; Dan Hua (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

An Efficient Method for Enrichment and In Vitro Propagation of Muscle Stem Cells Derived from Black Sea Bream (Acanthopagrus schlegelii) Skeletal Muscle - Dan Hee Han; Seung Pyo Gong (Marine Biotechnology, 2025)

Genetic estimation of fat traits in sheep and association of its NR1H4 gene polymorphisms with tail fat deposition - Kunchao Han; Fadi Li; Xiaoxue Zhang; Huibin Tian; Deyin Zhang; Kai Huang; Yuan zhao; Yukun Zhang; Liming Zhao; Dan Xu; Jiangbo Cheng; Zongwu Ma; et al. (Small Ruminant Research, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

Characterization of droplet freezing on superhydrophobic surfaces with different microstructures - Xu Han; Dan Zhang; Haikun Zheng; Wei Sheng; Xiaoru Hao; Xiaozhuan Chen; Chaobin Dang; Mengjie Song (Energy and Buildings, 2025)

What dominates the variation of ecosystem services across different urban expansion patterns?—Evidence from the Yangtze River Delta region, China - Dan Yi; Jie Guo; Steven G. Pueppke; Yi Han; Guanqiao Ding; Minghao Ou; Eric Koomen (Environmental Impact Assessment Review, 2025)

Silk fibroin for cosmetic dermatology - Songjie Li; Han Chen; Xin Dan; Yikun Ju; Tong Li; Bo Liu; Yang Li; Lanjie Lei; Xing Fan (Chemical Engineering Journal, 2025)

Graphene quantum dots decorated organic conductive polymer for advanced ternary amorphous solar-blind UV photovoltaic photodetectors - Han Cai; Haolin Yang; Weisen Li; Jiarong Liang; Zhuogeng Lin; Xingui Tang; Yanghui Liu; Dan Zhang; Wei Zheng (Chemical Engineering Journal, 2025)

The high molecular weight and large particle size and high crystallinity of starch increase gelatinization temperature and retrogradation in glutinous rice - Cheng Liang; Yiman Han; Haoyang Xu; Dan Liu; Chunyan Jiang; Qingyu Li; Yungao Hu; Xunchao Xiang (Carbohydrate Polymers, 2025)

Navβ2 Intracellular Fragments Contribute to Aβ1-42-Induced Cognitive Impairment and Synaptic Deficit Through Transcriptional Suppression of BDNF - Min-Nan Lu; Dan Wang; Chen-Jun Ye; Guo-Ji Yan; Jing-Feng Song; Xin-Ying Shi; Shan-Shan Li; Li-Na Liu; Hui-Xiang Zhang; Xiao-Han Dong; Tao Hu; Xu-Yang Wang; et al. (Molecular Neurobiology, 2025)

Roseobacter sinensis sp. nov., a marine bacterium capable to synthesize arachidonic acid - Hong-Chuan Wang; Meng-Han Huang; Dan-Yuan Guo; Wen-Li Liu; Zi-Wen Yang; Dao-Feng Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Investigation of rice debranning mechanism based on tribological behaviour between rice grains - Jiaming Fei; Ze Sun; Dan Zhao; Anqi Li; Fuguo Jia; Yanlong Han; Hao Li; Shouyu Ji; Zhuozhuang Li; Wenyu Feng (Biosystems Engineering, 2024)

Eicosatrienoic acid enhances the quality of in vitro matured porcine oocytes by reducing PRKN-mediated ubiquitination of CISD2 - Zhi-Yong An; Sheng-Zhong Han; Zhou-Yan Li; Shuang-Yan Chang; Xiu-Li Zhang; Gao-Jie Lu; Tuo Zhang; Biao-Hu Quan; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Nitrogen oxides emissions from coastal wetland sediments: Experimental assessment of the influence of vegetation and nitrogen input - Jiang-Chen Gong; Bing-Han Li; Chun-Ying Liu; Qin-Dao Li; Jing-Wen Hu; Pei-Feng Li; Dan He; Gui-Peng Yang (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

The interaction between plasma polymetals and lifestyle on cognitive dysfunction in occupational aluminum exposed workers: A cross-sectional study in China - Tianshu Wang; Lingshan Xue; Chenyang Li; Dan Zhao; Jiaping Huan; Xiao Han; Jing Song; Linping Wang; Huifang Zhang; Qiao Niu; Baolong Pan; Jinzhu Yin; et al. (NeuroToxicology, 2024)

AmTPS6 promotes trehalose biosynthesis to enhance the Cd tolerance in mangrove Avicennia marina - Ling-Yu Song; Jing Li; Lu-Dan Zhang; Zhao-Yu Guo; Chao-Qun Xu; Li-Wei Jiang; Jin-Yu Liu; Ji-Cheng Wang; Qing-Hua Li; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2024)

Spatial heterogeneity of volatile organic compound pollution in a typical industrial park based on multi-point online monitoring: Pollution characteristics, health risks, and priority-controlled species - Mengjuan Han; Ge Ren; Xinna Zhao; Xiaodong Zhang; Hong Lin; Dan Liu; Lei Wang (Atmospheric Environment, 2024)

Erratum to: Identification of Saline Soybean Varieties Based On Trinocular Vision Fusion and Deep Learning - Hang Liu; Qiong Wu; Guangxia Wu; Dan Zhu; Limiao Deng; Xiaoyang Liu; Zhongzhi Han; Longgang Zhao (Journal of Crop Health, 2024)

Identification of Saline Soybean Varieties Based On Trinocular Vision Fusion and Deep Learning - Hang Liu; Qiong Wu; Guangxia Wu; Dan Zhu; Limiao Deng; Xiaoyang Liu; Zhongzhi Han; Longgang Zhao (Journal of Crop Health, 2024)

Enhancing biomass and ecological sustainability in rice–fish cocropping systems through the induction of functional microbiota with compound biogenic bait - Yang Zhang; Ying-Han Liu; Dan-Yao Tang; Jun Zhang; Xi-Yue Zhang; Chen-Wei Xu; Yu-Juan Yuan; Chuan-Chao Dai (Soil Ecology Letters, 2024)

Activating employees’ organizational citizenship behavior toward the environment in China: a moderated mediation model - Zhiyong Han; Mingxia Chen; Chuanyun Jiang; Dan Wang (Environment, Development and Sustainability, 2024)

Meteorological effects of ventilation corridor in central urban areas: A case study of Wuhan - Xuesong Li; Kai Lin; Dan Cheng; Han Zou; Yulong Shu; Zhiguo Jin; Jiabei Zhu (Sustainable Cities and Society, 2024)

Polymorphisms of PRKAA1 and FABP4 genes and their association with feed efficiency in Hu sheep - Mengru Pu; Deyin Zhang; Liming Zhao; Dan Xu; Zongwu Ma; Kunchao Han; Lijuan He; Chengqi Yan; Qi Zhang; Lianjun Feng; Ziyue Xiao; Lei Gao; et al. (Small Ruminant Research, 2024)

Juvenile hormone inhibits lipogenesis of Spodoptera exigua to response to Bacillus thuringiensis GS57 infection - Bo Gao; Yujie Ji; Dan Zhao; Yitong Yan; Lu Zhang; Han Wu; Yifan Xie; Qiuyu Shi; Yao Wang; Wei Guo (Pesticide Biochemistry and Physiology, 2024)

Development of a novel amphibious robot with a reusable cycloidal propulsion module - Dan Xia; Han Yan; Yunde Shi; Jinming Wu; Xiang Luo (Ocean Engineering, 2024)

Safety-critical anti-disturbance control of tugs for collaborative berthing - Haodong Liu; Anqing Wang; Bing Han; Tieshan Li; Dan Wang; Zhouhua Peng (Ocean Engineering, 2024)

Unraveling the impact of disinfection treatment on the microbial community successions and quality attributes of green peppers (Capsicum annuum L.) during storage - Qianqian Jiang; Rongrong Lu; Zhihong Ma; Zhaoying He; Wanfu Hou; Mengtong Han; Pan Wang; Xiaoyan Zhao; Dan Wang (Food Research International, 2024)

Unlocking maize yield potential through exploring canopy-root interactions with nature-based nutrient management - Yupeng Zhu; Junhao Wang; Yongjun Zhu; Han Lai; Ziren Qu; Jian Zhao; Dan Wei; Pu Wang; Qingfeng Meng (Field Crops Research, 2024)

RNA reading protein YTHDF2 mediates Benzo(k)fluoranthene induced male reproductive injury by regulating the stability of BCL2 - Ya-wen Li; Dan-dan Wang; Hong-qiang Chen; Yong Zeng; Na Wang; Yu Shi; Jiang-ying Li; Ni-ya Zhou; Da-peng Wang; Qing Chen; Xue Han; Jia Cao; et al. (Environmental Pollution, 2024)

Weakly solvated electrolyte enables the robust solid electrolyte interface on SiOx anodes for lithium-ion battery - Zuojie Xu; Rong Huang; Pengfei Huang; Chaowei He; Shenwen Liu; Haonan Zheng; Wenlong Song; Lu Shi; Weiwei Gao; Dan Li; Hui Huang; Hangjun Ying; et al. (Chemical Engineering Journal, 2024)

Migration of membrane fouling with minimal damage to cell integrity by catalytic ceramic membrane systems in low dosages of ozone during algae-laden water treatment - Dan Song; Xiaodie Han; Jiahui Li; Wei Cheng; Caihong Liu; Chuandong Wu; Jie Qiu; Jun Ma; Zhiqiang Sun (Chemical Engineering Journal, 2024)

Sequence-Unconstrained DNA Computing: DSN cycling and PER circuitry for dynamic miRNAs analysis and multifunctional logic operations - Dan Bai; Yaoyi Zhang; Jiu Pu; Li Zhang; Hongyan Yu; Xiaole Han; Ke Lv; Li Wang; Junjie Li; Ao Tang; Wang Luo; You Wu; et al. (Chemical Engineering Journal, 2024)

Allosteric stem-loop multicomponent DNAzyme: A versatile stimuli-responsive switch for nanotweezer operations and multifunctional biosensing - Yaoyi Zhang; Dan Bai; Jiu Pu; Li Zhang; Weitao Wang; Tong Feng; Jianhong Zhang; Hongyan Yu; Xiaole Han; Ke Lv; Li Wang; Yongcan Guo; et al. (Chemical Engineering Journal, 2024)

Hohaiivirga grylli gen. nov., sp. nov., a New Member of the Family Methylobacteriaceae, Isolated from Cricket (Gryllus chinensis) - Hong-Chuan Wang; Meng-Han Huang; Dan-Yuan Guo; Wei He; Lu Wang; Zi-Yue Fu; Wen-Jun Li; Ai Hua Zhang; Dao-Feng Zhang (Current Microbiology, 2024)

Spatial and historical patterns of sedimentary organic matter sources and environmental changes in the Ross Sea, Antarctic: implication from bulk and n-alkane proxies - Dan Yang; Wenshen Chen; Wenhao Huang; Haisheng Zhang; Zhengbing Han; Bing Lu; Jun Zhao (Frontiers in Marine Science, 2024)
Organic carbon (OC) burial in the Antarctic marginal seas is essential for regulating global climate, particularly due to its association with ice shelf retreat. Here, we analyzed total OC (TOC), total nitrogen (TN), radiocarbon isotope, n -alkanes and relative indicators in surface and core sediments from the Ross Sea, West Antarctica. Our aim was to investigate spatial and historical changes in OC sources, and to explore the influencing factors and implications for ice shelf retreat since the last glacial maximum (LGM). Our results revealed distinct spatial patterns of OC sources as indicated by n -alkane indicators in surface sediments. In the Western Ross Sea, n -alkanes predominantly originated from phytoplankton and bacteria, as evidenced by their unimodal distribution, low carbon preference index (CPI) of short-chain n -alkanes (CPI L = 1.41 ± 0.30), and low terrestrial/aquatic ratio (TAR = 0.22 ± 0.14). In the Southwest Ross Sea, n -alkanes were derived from marine algae and terrestrial bryophytes, indicated by bimodal distribution, low ratio of low/high molecular-weight n -alkanes (L/H = 0.62 ± 0.21), low CPI of long-chain n -alkanes (CPI H = 1.18 ± 0.16), and high TAR (1.26 ± 0.66). In contrast, the Eastern Ross Sea exhibited n -alkanes that were a combination of phytoplankton and dust from Antarctic soils and/or leaf waxes from mid-latitude higher plant, as suggested by both unimodal and bimodal distributions, high L/H (1.60 ± 0.58) and CPI H (2.04 ± 0.28), and medium TAR (0.61 ± 0.30). Geologically, during the LGM (27.3 – 21.0 ka before present (BP)), there was an increased supply of terrestrial OC (TOC/TN = 13.63 ± 1.29, bimodal distribution of n -alkanes with main carbon peaks at n C 17 / n C 19 and n C 27 ). From 21.0 to 8.2 ka BP, as glaciers retreated and temperatures rose, the proportion of marine n -alkanes significantly increased (TOC/TN = 9.09 ± 1.82, bimodal distribution of n -alkanes with main carbon peaks at n C 18 / n C 19 and n C 25 ). From 8.2 ka BP to the present, as the ice shelf continued to retreat to its current position, the marine contribution became dominant (TOC/TN = 8.18 ± 0.51, unimodal distribution of n -alkanes with main carbon peak at n C 17 / n C 18 / n C 19 , and low TAR (0.41 ± 0.32)). This research has significant implications for understanding the variations in Antarctic OC sources and their climatic impacts in the context of accelerated glacier melting.

Spatiotemporal variations and source on black carbon over Chongqing, China: Long-term changes and observational experiments - Yurong Zhang; Yong Han; Li Dong; Ximing Deng; Dan Ye; Shiyong Shao (Science of The Total Environment, 2024)

The disruptive effect on the bacterial cell wall explored of the ultrasmall particle-sized Ag nanoparticles supported with Zn Cu-based hybrid nanoagents - Shaobo Guo; Xu Liu; Huihui Chen; Yanming Qiao; Zhifeng Liu; Dan Zhang; Guo Ting; Xiaohui Ji; Hao Han; Tanlei Zhang (Journal of Environmental Chemical Engineering, 2024)

Design of enhanced entropy-driven non-covalent DNA catalytic reactions via the paired junction structure - Weitao Wang; Hongyan Yu; Xiaole Han; Li Zhang; Zhi Weng; Chen Zuo; Na Yin; Yaoyi Zhang; Tong Feng; Dan Bai; Ao Tang; Yongcan Guo; et al. (Chemical Engineering Journal, 2024)

Inorganic salts released from polypyrrole nanocapsules on compact TiO2 layer for highly efficient inorganic CsPbI3-type perovskite solar cells - Dan Li; Xin Li; Kang Wang; Simin Ma; Xin Shao; Tingting Yang; Yunhui Han; Zhengguo Zhang; Shengzhong Liu; Shengwei Guo (Chemical Engineering Journal, 2024)

The value of pocket parks in preserving urban butterfly diversity - Shujing Zhang; Dan Han; Junying She; Qing Shen; Cheng Wang (Urban Forestry & Urban Greening, 2024)

Quercetin alleviates kidney damage caused by mercury Chloride: The protective effects of quercetin on autophagy and inflammation were studied based on TRIM32/TLR4/LC3 pathway - Fan Jin; JiaYue Li; Chenyu Zhao; Lixiang Gu; Min Pu; Simin Jiang; Mingming Liang; Ying Zhao; Jianli Shen; Agabuwei Agabuwei; Qin Han; Dan Liao (Toxicon, 2024)

Expression of ovine MYH3 gene and its polymorphisms and association analysis with growth traits in Hu sheep - Kunchao Han; Fadi Li; Xiaoxue Zhang; Huibin Tian; Deyin Zhang; Kai Huang; Yukun Zhang; Yuan Zhao; Liming Zhao; Dan Xu; Jiangbo Cheng; Zongwu Ma; et al. (Small Ruminant Research, 2024)

Development of a multi-tentacled collaborative underwater robot with adjustable roll angle for each tentacle - Zhihan Li; Qingyuan Gai; Ming Lei; Han Yan; Dan Xia (Ocean Engineering, 2024)

Characterisation of a SapYZU11@ZnFe2O4 biosensor reveals its mechanism for the rapid and sensitive colourimetric detection of viable Staphylococcus aureus in food matrices - Wenyuan Zhou; Aiping Deng; Xiaoxing Fan; Yeling Han; Yajun Gao; Lei Yuan; Xiangfeng Zheng; Dan Xiong; Xuechao Xu; Guoqiang Zhu; Zhenquan Yang (Food Microbiology, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

In-situ chemical state transition of Ni nano-metal catalytic site promotes the reaction kinetics of lithium-sulfur battery - Chunman Yang; Fei Wang; Dan You; Wenhao Yang; Yongqi Wang; Wenchang Han; Yiyong Zhang; Ziyi Zhu; Xue Li (Chemical Engineering Journal, 2024)

Machine-learning-assisted n-GaN-Au/PANI gas sensor array for intelligent and ultra-accurate ammonia recognition - Dan Han; Yu Wang; Yuxuan Wang; Qi Duan; Donghui Li; Yang Ge; Xiuli He; Li Zhao; Weidong Wang; Shengbo Sang (Chemical Engineering Journal, 2024)

Efficient antibacterial and microbial corrosion resistant photocatalytic coating: Enhancing performance with S-type heterojunction and Cu synergy - Mankun Li; Zishuai Hu; Dan Liu; Yongmei Liang; Shijia Liu; Bo Wang; Chunmei Niu; Dake Xu; Jianhui Li; Baochen Han (Chemical Engineering Journal, 2024)

Non-pyrolytic synthesis of laccase-like iron based single-atom nanozymes for highly efficient dual-mode colorimetric and fluorescence detection of epinephrine - Yu-Han Shi; Wen-Cai Jiang; Jing Zeng; Si-Yan Wang; Wei Wu; Shu-Dan Xie; Yan Zhao; Zhi-Hong Xu; Guo-Qi Zhang (Analytica Chimica Acta, 2024)

A review of the polyphenols purification from apple products - Lu Wang; Hanyue Wang; Dan Liu; Zhiwu Han; Jianhua Fan (Critical Reviews in Food Science and Nutrition, 2024)

Wastewater threshold as an indicator of COVID-19 cases in correctional facilities for public health response: A modeling study - Dan Han; Pamela Linares; Rochelle H. Holm; Kartik Chandran; Ted Smith (Water Research, 2024)

Prenatal and postnatal early life exposure to greenness and particulate matter of different size fractions in relation to childhood rhinitis - A multi-center study in China - Liu Yang; Han Chen; Huiyu Gao; Ying Wang; Tianyi Chen; Magnus Svartengren; Dan Norbäck; Jing Wei; Xiaohong Zheng; Ling Zhang; Chan Lu; Wei Yu; et al. (Science of The Total Environment, 2024)

Comprehensive comparison of aroma profiles and chiral free and glycosidically bound volatiles in Fujian and Yunnan white teas - Han Yan; Wei-Xuan Li; Ying-Lin Zhu; Zhi-Yuan Lin; Dan Chen; Yue Zhang; Hai-Peng Lv; Wei-Dong Dai; De-Jiang Ni; Zhi Lin; Yin Zhu (Food Chemistry, 2024)

Ammonia detection based on Pd/Rh-GaN and recognition of disease markers of nitrogen compounds assistant by deep learning - Jiexu Shi; Dan Han; Yuxuan Wang; Qi Duan; Hongwei Li; Xiaqin Zhang; Hua Liang; Shengbo Sang (Chemical Engineering Journal, 2024)

Targeting GLUT1 degradation with assembling glycopeptide for cancer inhibition - Xia Wu; Jun Shen; Xingyue Jiang; Hong Han; Zenghui Li; Yatong Xiang; Dan Yuan; Junfeng Shi (Chemical Engineering Journal, 2024)

Risk Factors for Preoperative Cerebral Infarction in Infants with Moyamoya Disease - Qingbao Guo; Songtao Pei; Qian-Nan Wang; Jingjie Li; Cong Han; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; Zhengxing Zou; et al. (Translational Stroke Research, 2024)

Mining for QTL controlling maize low-phosphorus response genes combined with deep resequencing of RIL parental genomes and in silico GWAS analysis - Bowen Luo; Peng Ma; Chong Zhang; Xiao Zhang; Jing Li; Junchi Ma; Zheng Han; Shuhao Zhang; Ting Yu; Guidi Zhang; Hongkai Zhang; Haiying Zhang; et al. (Theoretical and Applied Genetics, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Effects of dietary hot water extracts of Chlorella vulgaris on muscle component, non-specific immunity, antioxidation, and resistance to non-ionic ammonia stress in Pacific white shrimp Litopenaeus vannamei - Dan Zhang; Shuyi Shi; Xuying Jia; Wenli Zhou; Xiaoyu Sun; ChaoJie Han; Yunliang Lu (Frontiers in Marine Science, 2024)
Hot water extract of Chlorella vulgaris (CVE) is a biologically substance that enhances organism’s immune function and antioxidative capacity. This study evaluated the effect of supplementation with various concentrations of CVE on muscle nutritional components, non-specific immunity, antioxidation, and resistance to non-ionic ammonia (NH 3 -N) stress in Litopenaeus vannamei over 45 days using diets supplemented with CVE at five different concentrations (0%, 0.5%, 1%, 5%, 10%, and 15%). Specifically, fresh and sweet amino acids (Asp, Glu) significantly increased ( P < 0.05) in shrimp fed the 1% CVE diet, reaching 18.12 g/kg and 33.08 g/kg, respectively. Bitter amino acids (Leu) and Hypoxanthine (Hx) significantly decreased ( P < 0.05) in shrimp fed the 1% CVE diet, at 10.56 g/kg and 10.56 ug/g. CVE supplementary enhanced the activities of acid phosphatase, alkaline phosphatase, and nitric oxide synthase while decreasing malondialdehyde levels. Shrimp fed with a 1% CVE diet exhibited significantly higher enzyme activity than the control group under NH 3 -N conditions ( P < 0.05). Overall, this study demonstrated that 1% CVE as a feed additive significantly improved the muscle mass, boosted immunity and reduced the stress response to NH 3 -N in L. vannamei . This research provides a valuable reference for the application of CVE as a feed additive in crustacean aquaculture.

Upper Ocean Responses to Tropical Cyclone Mekunu (2018) in the Arabian Sea - Dan Ren; Shuzong Han; Shicheng Wang (Journal of Marine Science and Engineering, 2024)
Based on Argo observations and a coupled atmosphere–ocean–wave model, the upper ocean responses to the tropical cyclone (TC) Mekunu (2018) were investigated, and the role of a pre-existing cold eddy in modulating the temperature response to TC Mekunu was quantified by employing numerical experiments. With TC Mekunu’s passage, the mixed layer depth (MLD) on both sides of its track significantly deepened. Moreover, two cold patches (

Ppb-level unsymmetrical dimethylhydrazine detection based on In2O3 hollow microspheres with Nd doping - Weiyi Bu; You Zhou; Dan Huang; Na Liu; Yan Zhang; Wenjiang Han; Xiaohong Chuai; Zhijie Zhou; Changhua Hu; Geyu Lu (Journal of Hazardous Materials, 2024)

Adapting to diversified garlic-maize rotation systems by adjusting nitrogen application: Assessing crop yield, nitrogen utilization, and nitrogen footprint - Dan Liu; Qin Mo; Wei Zhang; Wei Lin; Wenjing Li; Maksat Batyrbek; Ruixia Ding; Hui Li; Baoping Yang; Yufeng Zou; Li Wang; Yantai Gan; et al. (Journal of Cleaner Production, 2024)

Microfluidic paper-based analysis device applying black phosphorus nanosheets@MWCNTs-COOH: A portable and efficient strategy for detection of β-Lactoglobulin in dairy products - Xintong Han; Dan Zhang; Mengjiao Xie; Jingying Yang; Yueyao Wang; Huilin Li; Shuo Wang; Mingfei Pan (Food Chemistry, 2024)

Synthesis of MOF-5/polyethersulfone (PES) mixed matrix membranes for enhancing membrane filtration performance in polyphenol purification - Lu Wang; Jingzhe Huang; Jianhua Fan; Zhiwu Han; Dan Liu (Environmental Research, 2024)

Highly efficient conversion of biomass-derived furanic compounds into alkyl diols by selective hydrogenolysis using non-noble metal catalysts with tunable surface oxygen vacancies - Kang Zhou; Yongsheng Zhang; Mengyuan Zhang; Armin Rezayan; Zhen Quan; Dandan Han; Jianshe Wang; Dan Wu; Chunbao Xu (Chemical Engineering Journal, 2024)

Decitabine-based nanoparticles for enhanced immunotherapy of hepatocellular carcinoma via DNA hypermethylation reversal - Hongqiao Cai; Xiaocheng Li; Yahui Liu; Jianji Ke; Kaiyu Liu; Yixin Xie; Cheng Xie; Dan Zhou; Mingda Han; Bai Ji (Chemical Engineering Journal, 2024)

Exploring the phosphorus–starch content balance mechanisms in maize grains using GWAS population and transcriptome data - Bowen Luo; Haiying Zhang; Zheng Han; Xiao Zhang; Jianyong Guo; Shuhao Zhang; Xianfu Luo; Jin Zhao; Wei Wang; Guohui Yang; Chong Zhang; Jing Li; et al. (Theoretical and Applied Genetics, 2024)

Reindeer (Rangifer tarandus) hindlimb joint kinetics: propulsive and energy storage mechanisms and mechanical work - Guoyu Li; Rui Zhang; Hao Pang; Junfeng Wang; Dan Jin; Xumin Sun; Dianlei Han; Zhisong Li; Lige Wen (Polar Biology, 2024)

Fourteen undescribed steroidal saponins from Solanum capsicoides leaves and their neuroprotective effects - Yan Liu; Xin-Yuan Li; Jia-tong Wu; Han Wang; Xin Meng; Hai-Dan Zou; Juan Pan; Wei Guan; Adnan Mohammed Algradi; Anam Naseem; Hai-Xue Kuang; Bing-You Yang (Phytochemistry, 2024)

BmNPV p35 regulates apoptosis in Bombyx mori via a novel target of interaction with the BmVDAC2-BmRACK1 complex - Lin-Bao Zhu; Han-Dan Zhu; Zhi-Hao Huang; Hui-Hua Cao; Sadaf Ayaz; Jia-Yue Yang; Xi-Ya Chen; Ying Zhang; Shi-Huo Liu; Jia-Ping Xu (Insect Biochemistry and Molecular Biology, 2024)

Greenness and its composition and configuration in association with allergic rhinitis in preschool children - Han Chen; Xia Meng; Yongfu Yu; Jin Sun; Zhiping Niu; Jing Wei; Ling Zhang; Chan Lu; Wei Yu; Tingting Wang; Xiaohong Zheng; Dan Norbäck; et al. (Environmental Research, 2024)

Is cryoablation still suitable for advanced non-small cell lung cancer after failure of first-line chemotherapy? A multicenter, prospective, randomized-controlled trial of eighty-seven patients - Yu Chen; Xueni Fang; Dan Wang; Quanwang Li; Kerui Zhang; Yuan Li; Jinghua Li; Haoyue Pang; Zhiqiang Cheng; Chunyang Zhang; Caiyun Zhang; Wuwei Yang; et al. (Cryobiology, 2024)

Copper exposure induces inflammation and PANoptosis through the TLR4/NF-κB signaling pathway, leading to testicular damage and impaired spermatogenesis in Wilson disease - Dan Zhao; Limin Wu; Xinru Fang; Luyao Wang; Qianzhuo Liu; Pengyu Jiang; Zhihui Ji; Nian Zhang; Miaozhu Yin; Hui Han (Chemico-Biological Interactions, 2024)

Effects of Mesenchymal Stem Cells-Derived Extracellular Vesicles on Inhibition of Hepatic Fibrosis by Delivering miR-200a - Ai-Lei Xu; Long Han; Jun Yan; Dan Liu; Wei Wang (Tissue Engineering and Regenerative Medicine, 2024)

Quantifying the Health Risks of PM2.5-Bound Heavy Metals for Rural Populations with Different Energy Use Types During the Heating Season - Wenju Wang; Mingya Wang; Mingshi Wang; Xuechun Zhang; Qiao Han; Chun Chen; Dan Liu; Qinqing Xiong; Chunhui Zhang (Exposure and Health, 2024)

Identification of lignans as ATP citrate lyase (ACLY) inhibitors from the roots of Pouzolzia zeylanica - Jin-Long Li; Jia-Yi Jiang; Shan-Shan Gu; Lei Zhang; Yan Sun; Xue-Han Wang; Dan-Yu Li; Zhe-Yu Chen; Sheng-Shi Jiang; Wei-Zhong Zhu; Hao-Wen Jiang; Hong-Jie Zhang (Natural Product Research, 2024)

Bioinsecticide PA1b alleviates lipopolysaccharide-induced inflammation and impairment of bovine mammary epithelial cells - Peng Dan; Han Zhao; Jiahui Xi; Yanying Zhao (Pesticide Biochemistry and Physiology, 2024)

CRISPR/Cas12a powered air-displacement enhanced evanescent wave fluorescence fiber-embedded microfluidic biochip for nucleic acid amplification-free detection of Escherichia coli O157:H7 - Xiangzhi Han; Dan Song; Wenjuan Xu; Laiya Lu; Anna Zhu; Feng Long (Journal of Hazardous Materials, 2024)

Core microbes identification and synthetic microbiota construction for the production of Xiaoqu light-aroma Baijiu - Huan Wang; Yumei Wang; Yulei Ruan; Dan Ma; Han Wang; Shengzhi Yang; Linjie Lyu; Fengjun Yang; Xiaole Wu; Yefu Chen (Food Research International, 2024)

Driving soil N2O emissions under nitrogen application by soil environmental factor changes in garlic-maize rotation systems - Dan Liu; Chi Ma; Yang Liu; Qin Mo; Wei Lin; Wenjing Li; Hui Li; Baoping Yang; Ruixia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2024)

Impact of reclamation projects on water quality in jinmeng bay, China - Cuiping Kuang; Dan Wang; Gang Wang; Jiantao Liu; Xuejian Han; Yan Li (Estuarine, Coastal and Shelf Science, 2024)

Self-supporting honeycomb coaxial carbon fibers: A new strategy to achieve an efficient hydrogen evolution reaction both in base and acid media - Jiaqi Lin; Duanduan Yin; Wurigamula He; Lili Wang; Bin Yue; Tianqi Wang; Dan Li; Ce Han; Xiangting Dong (Chemical Engineering Journal, 2024)

Effect of multi-interface electron transportation and molecule adsorption on hydrogen evolution reaction - Xinyu Zhang; Zhihui Li; Xiaoman Yang; Hanming Zhang; Dan Wang; Zhian Li; Chengyue Han; Bingzheng Dong; Zhisheng Mei; Fei Teng (Chemical Engineering Journal, 2024)

A multimodal virtual vision platform as a next-generation vision system for a surgical robot - Young Gyun Kim; Jong Hyeon Lee; Jae Woo Shim; Wounsuk Rhee; Byeong Soo Kim; Dan Yoon; Min Jung Kim; Ji Won Park; Chang Wook Jeong; Han-Kwang Yang; Minwoo Cho; Sungwan Kim (Medical & Biological Engineering & Computing, 2024)
Robot-assisted surgery platforms are utilized globally thanks to their stereoscopic vision systems and enhanced functional assistance. However, the necessity of ergonomic improvement for their use by surgeons has been increased. In surgical robots, issues with chronic fatigue exist owing to the fixed posture of the conventional stereo viewer (SV) vision system. A head-mounted display was adopted to alleviate the inconvenience, and a virtual vision platform (VVP) is proposed in this study. The VVP can provide various critical data, including medical images, vital signs, and patient records, in three-dimensional virtual reality space so that users can access medical information simultaneously. An availability of the VVP was investigated based on various user evaluations by surgeons and novices, who executed the given tasks and answered questionnaires. The performances of the SV and VVP were not significantly different; however, the craniovertebral angle of the VVP was 16.35° higher on average than that of the SV. Survey results regarding the VVP were positive; participants indicated that the optimal number of displays was six, preferring the 2 × 3 array. Reflecting the tendencies, the VVP can be a neoconceptual candidate to be customized for medical use, which opens a new prospect in a next-generation surgical robot. Graphical Abstract

Parallel path following control of cyber-physical maritime autonomous surface ships based on deep neural predictor - Lingfeng Li; Anqing Wang; Bing Han; Dan Wang; Tieshan Li; Zhouhua Peng (Ocean Engineering, 2024)

Electrically conductive coals in nature: Their traits, whereabouts, green-exploitations and impacts - Busheng Zhang; Hongming Chen; Zhiqiang Han; Liyin Song; Zijin Liu; Woon-Ming Lau; Dan Zhou (Fuel, 2024)

All-in-one chitosan-based aerogel with a semi-clad structure for solar-driven interfacial evaporation - Yiwen Xue; Xinhong Han; Dan Xu; Zihang Zhang; Lingjun Zhu; Shurong Wang (Desalination, 2024)

The construction of a microalgal-bacterial biofilm reactor for enhanced swine wastewater treatment - Huichao Zhang; Tianhao Wu; Liqin Sun; Zhiyu Han; Qianchang Wang; Dan Li (Algal Research, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Mechanism of methylmercury photodegradation in the yellow sea and East China Sea: Dominant pathways, and role of sunlight spectrum and dissolved organic matter - Dan Li; Xiaoxiao Han; Yanbin Li (Water Research, 2024)

Microplastics affect mosquito from aquatic to terrestrial lifestyles and are transferred to mammals through mosquito bites - Jian-hang Li; Xiao-hui Liu; Guo-rui Liang; He-ting Gao; Si-han Guo; Xin-yu Zhou; Dan Xing; Teng Zhao; Chun-xiao Li (Science of The Total Environment, 2024)

Illustrating China's journey to balance, circular, and secure potassium cycles in the last three decades - Yan-Fei Liu; Peng Wang; Dan-Yi Feng; Xiaojie Liu; Zhongkui Han; Tao Dai; Shou-Ting Zhang; Wei-Qiang Chen (Resources, Conservation and Recycling, 2024)

IGF1R stimulates autophagy, enhances viability, and promotes insulin secretion in pancreatic β cells in gestational diabetes mellitus by upregulating ATG7 - Qing Liu; Ying Han; Meng Zhang; Peng Yang; Yan Xiang; Min Chen; Fei Xu; Xiaochan Zhou; Dan Zheng; Juan Qin (Reproductive Biology, 2024)

Bbhox2 is a key regulator for conidiation and virulence in Beauveria bassiana - Juanjuan Li; Yan Zhang; Shouhao Jiao; Lian He; Yanhua Fan; Xuemeng Han; Binda Sun; Wenqi Zhao; Yanlin Mei; Ning Wei; Haiyue Zeng; Dan Jin (Journal of Invertebrate Pathology, 2024)

Monospecific and ultrasensitive detection of ofloxacin: A computational chemistry-assisted hapten screening strategy and analysis of molecular recognition mechanism - Jiaxu Xiao; Liangni Qin; Dan Zhao; Niexie Huang; Wennuo Xu; Linwei Zhang; Xiaoming Pan; Shiyun Han; Mingyue Ding; Long Li; Tao Le; Dapeng Peng (Journal of Hazardous Materials, 2024)

Prenatal exposure to poly- and perfluoroalkyl substances and postpartum depression in women with twin pregnancies - Liqin Hu; Hong Mei; Xiaonan Cai; Lulu Song; Qiao Xu; Wenqi Gao; Dan Zhang; Jieqiong Zhou; Chen Sun; Yi Li; Feiyan Xiang; Youjie Wang; et al. (International Journal of Hygiene and Environmental Health, 2024)

A sulfur-rich copolymer hybrid cathode for anchoring polysulfides and accelerating redox reaction in lithium sulfur batteries - Dan Liu; Xinmin Zhang; Yiting Wang; Xiaoguang Wang; Ying Han; Danchen Wang; Shengjing Guan; Haonan Weng; Haitao Xu; Changlong Sun; Yan-Jie Wang (Chemical Engineering Journal, 2024)

Shaping the succession patterns of different soil nutrients, enzyme stoichiometry, and microbial communities through rotation systems - Dan Liu; Yang Liu; Junjie Li; Qin Mo; Junyan Tang; Wenhan Liu; Maksat Batyrbek; Tiening Liu; Xudong Zhang; Qingfang Han (CATENA, 2024)

Effect of saline water drip irrigation on tomato yield and quality in semi-humid area and arid area of China - Xiaoyu Han; Dan Li; Yaohu Kang; Shuqin Wan (Irrigation Science, 2024)

Microfluidic platform for omics analysis on single cells with diverse morphology and size: A review - Shujin Lin; Dan Feng; Xiao Han; Ling Li; Yao Lin; Haibing Gao (Analytica Chimica Acta, 2024)

Man-in-the-Loop Control and Mission Planning for Unmanned Underwater Vehicles - Mengxue Han; Jialun Wang; Jianya Yuan; Zhao Wang; Dan Yu; Qianqian Zhang; Hongjian Wang (Journal of Marine Science and Engineering, 2024)
UUVs (unmanned underwater vehicles) perform tasks in the marine environment under direction from a commander through a mother ship control system. In cases where communication is available, a UUV task re-planning system was designed to ensure task completion despite uncertain events faced by UUVs. First, the XML language standardizes the expression of UUV task elements. Second, considering the time sequence and spatial path planning requirements of human-supervised UUV control tasks, time sequence planning based on a genetic algorithm and spatial path planning based on an improved genetic algorithm were designed to plan near-optimal approximate spatial paths for control tasks. Third, uncertainties encountered during UUV task execution were classified so that the commander could adjust according to the situation or invoke the control task re-planning algorithm to re-plan. Finally, a simulation platform was built using the QT development environment to simulate human-supervised UUV control task planning and re-planning, verifying the algorithm’s design effectiveness.

Effects of light spectra on the ovarian maturation and maternal immunity in the little yellow croaker (Larimichthys polyactis) - Ming Ming Han; Wei Zhan; Xiao Liang; Dan Dan Guo; Wan Tu Xu; Bao Lou (Aquaculture, 2024)

Biodegradable PBAT microplastics adversely affect pakchoi (Brassica chinensis L.) growth and the rhizosphere ecology: Focusing on rhizosphere microbial community composition, element metabolic potential, and root exudates - Yujuan Han; Ying Teng; Xiao Wang; Dan Wen; Peixin Gao; Dong Yan; Ning Yang (Science of The Total Environment, 2024)

Prenatal exposure to organophosphate esters and growth trajectory in early childhood - Wenyu Liu; Dan Luo; Aifen Zhou; Han Li; Adrian Covaci; Shunqing Xu; Surong Mei; Yuanyuan Li (Science of The Total Environment, 2024)

Molybdenum inhibited the growth of Phytophthora nicotiana and improved the resistance of Nicotiana tabacum L. against tobacco black shank - Bingjie Yu; Junling Li; Mohamed G. Moussa; Wenchao Wang; Shaosen Song; Zicheng Xu; Huifang Shao; Wuxing Huang; Yongxia Yang; Dan Han; Bingjun Dang; Jiayang Xu; et al. (Pesticide Biochemistry and Physiology, 2024)

Methylmercury-sensitized “turn on” SERS-active peroxidase-like activity of carbon dots/Au NPs nanozyme for selective detection of ochratoxin A in coffee - Qiulan Li; Qinqin Han; Dezhi Yang; Kexiang Li; Yijie Wang; Dan Chen; Yaling Yang; Hong Li (Food Chemistry, 2024)

A rational designed synthetic three-species alliance system for synergetic improvement on power generation from microbial fuel cell - Jun-Ying Han; Han-Lei Zhang; Hui Guo; An-Qi Liu; Said Nawab; Na Liu; Ming Hui; Dan-Dan Zhai; Yang-Chun Yong (Chemical Engineering Journal, 2024)

Insidious transmission of Mycobacterium tuberculosis in Ordos, China: a molecular epidemiology study - Hailin Sun; Zichun Ma; Fuli Ai; Bing Han; Peng Li; Juan Liu; Yiheng Wu; Yufeng Wang; Bing Li; Dan Qi; Yu Pang (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Establishment and Characterization of a Skeletal Muscle-Derived Myogenic Cell Line from Black Sea Bream (Acanthopagrus schlegelii) - Dan Hee Han; Seung Pyo Gong (Journal of Marine Science and Engineering, 2024)
Establishing muscle lineage cell lines from fish will provide a great opportunity to study muscle development, which can eventually contribute to the improvement of the fish quality in the aquaculture industry. However, there has been a lack of the development of proper fish muscle lineage cell lines so far. Here, we report the establishment of a skeletal muscle-derived myogenic cell line from black sea bream (Acanthopagrus schlegelii). For this, we first attempted to find the optimal conditions for the primary explant culture of A. schlegelii muscle tissues and then established muscle-derived cell lines. After that, cell lines were characterized for their muscle-specific gene expression, growth, and myogenic differentiation. We found that the primary explant culture was effective when the tissue fragments were cultured in Dulbecco’s Modified Eagle Medium supplemented with fetal bovine serum and antibiotics on gelatin-coated dishes. Additionally, we confirmed that the addition of basic fibroblast growth factor was necessary to establish the cell lines. One of three cell lines established was capable of long-term culture, expressed three major myogenic regulatory genes including Pax7, MyoD, and Myog, and differentiated to myotubes in the condition using low concentration of horse serum, demonstrating that this cell line was a skeletal muscle-derived myogenic cell line.

Laccase-evoked removal of antibiotics: Reaction kinetics, conversion mechanisms, and ecotoxicity assessment - Kai Sun; Mei-Hua Chen; Xue-Min Qi; Dan Hong; Ling-Zhi Dai; Shun-Yao Li; Yi-Chen Lu; Han-Qing Yu (Critical Reviews in Environmental Science and Technology, 2024)

Selenium-molybdenum interactions reduce chromium toxicity in Nicotiana tabacum L. by promoting chromium chelation on the cell wall - Lili Qu; Zicheng Xu; Wuxing Huang; Dan Han; Bingjun Dang; Xiaohan Ma; Yizan Liu; Jiayang Xu; Wei Jia (Journal of Hazardous Materials, 2024)

Sensitivity analysis of magnetic susceptibility under different climatic conditions during the late Pleistocene-Holocene period - Yuqian Han; Gang Liu; Chenxi Dan; Ya Liu; Qiong Zhang; Xiaolin Xia; Yang Zhang; Zhen Guo (CATENA, 2024)

Cyclophosphamide reduces gene transcriptional activity and embryo in vitro development by inhibiting NF-κB expression through decreasing AcH4K12 - Zhao-Bo Luo; Liu-Hui Yang; Sheng-Zhong Han; Shuang-Yan Chang; Hongye Liu; Zhi-Yong An; Xiu-Li Zhang; Biao-Hu Quan; Xi-Jun Yin; Jin-Dan Kang (Chemico-Biological Interactions, 2024)

Homer1 ameliorates ischemic stroke by inhibiting necroptosis-induced neuronal damage and neuroinflammation - Weihao Lv; Qianqian Zhang; Yuanming Li; Dan Liu; Xiuquan Wu; Xin He; Yuanyuan Han; Xiaowei Fei; Lei Zhang; Zhou Fei (Inflammation Research, 2024)
Objective Proinflammatory necroptosis is the main pathological mechanism of ischemic stroke. Homer scaffolding protein 1 (Homer1) is a postsynaptic scaffolding protein that exerts anti-inflammatory effects in most central nervous system diseases. However, the relationship between Homer1 and proinflammatory necroptosis in ischemic stroke remains unclear. Aim This study aimed to investigate the role of Homer1 in ischemia-induced necroptosis. Methods C57BL/6 mice were used to establish a model of permanent middle cerebral artery occlusion model (pMCAO). Homer1 knockdown mice were generated using adeno-associated virus (AAV) infection to explore the role of Homer1 and its impact on necroptosis in pMCAO. Finally, Homer1 protein was stereotaxically injected into the ischemic cortex of Homer1 flox/flox /Nestin-Cre +/− mice, and the efficacy of Homer1 was investigated using behavioral assays and molecular biological assays to explore potential mechanisms. Results Homer1 expression peaked at 8 h in the ischemic penumbral cortex after pMCAO and colocalized with neurons. Homer1 knockdown promoted neuronal death by enhancing necroptotic signaling pathways and aggravating ischemic brain damage in mice. Furthermore, the knockdown of Homer1 enhanced the expression of proinflammatory cytokines. Moreover, injection of Homer1 protein reduced necroptosis-induced brain injury inhibited the expression of proinflammatory factors, and ameliorated the outcomes in the Homer1 flox/flox /Nestin-Cre +/− mice after pMCAO. Conclusions Homer1 ameliorates ischemic stroke by inhibiting necroptosis-induced neuronal damage and neuroinflammation. These data suggested that Homer1 is a novel regulator of neuronal death and neuroinflammation.

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

The protective immunity induced by Trichinella spiralis galectin against larval challenge and the potential of galactomannan as a novel adjuvant - Ru Zhang; Xin Zhuo Zhang; Xin Guo; Lu Lu Han; Bo Ning Wang; Xi Zhang; Ruo Dan Liu; Jing Cui; Zhong Quan Wang (Research in Veterinary Science, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

AUV Collision Avoidance Planning Method Based on Deep Deterministic Policy Gradient - Jianya Yuan; Mengxue Han; Hongjian Wang; Bo Zhong; Wei Gao; Dan Yu (Journal of Marine Science and Engineering, 2023)
Collision avoidance planning has always been a hot and important issue in the field of unmanned aircraft research. In this article, we describe an online collision avoidance planning algorithm for autonomous underwater vehicle (AUV) autonomous navigation, which relies on its own active sonar sensor to detect obstacles. The improved particle swarm optimization (I-PSO) algorithm is used to complete the path planning of the AUV under the known environment, and we use it as a benchmark to improve the fitness function and inertia weight of the algorithm. Traditional path-planning algorithms rely on accurate environment maps, where re-adapting the generated path can be highly demanding in terms of computational cost. We propose a deep reinforcement learning (DRL) algorithm based on collision avoidance tasks. The algorithm discussed in this paper takes into account the relative position of the target point and the rate of heading change from the previous timestep. Its reward function considers the target point, running time and turning angle at the same time. Compared with the LSTM structure, the Gated Recurrent Unit (GRU) network has fewer parameters, which helps to save training time. A series of simulation results show that the proposed deep deterministic policy gradient (DDPG) algorithm can obtain excellent results in simple and complex environments.

Analysis of volatile organic compounds and potential odour compounds in food contact paperboard using headspace two-dimensional GC-QTOF-MS - Dan Li; Ying Zeng; Zhi-Kang Ye; Han-Ke Li; Yu-Zhe Li; Ben Dong; Qi-Zhi Su; Qin-Bao Lin; Jing Xiao; Huai-Ning Zhong (Food Additives & Contaminants: Part A, 2023)

Impacts of Nile Tilapia (Oreochromis niloticus) exposed to microplastics in bioflocs system - Xin Hu; Liu-Jiang Meng; Han-Dan Liu; Yan-Shuo Guo; Wen-Chang Liu; Hong-Xin Tan; Guo-Zhi Luo (Science of The Total Environment, 2023)

Online learning-based active disturbance rejection control of autonomous surface vehicles with HIL simulations - Bo Peng; Nan Gu; Dan Wang; Tieshan Li; Bing Han; Zhouhua Peng (Ocean Engineering, 2023)

Numerical investigation on self-propelled hydrodynamics of squid-like multiple tentacles with synergistic expansion - Zhihan Li; Dan Xia; Ming Lei; Han Yan (Ocean Engineering, 2023)

By reconstructing a multifunctional intensive microbiome, effective microorganisms (EM) improve the ecological environment of rice–crayfish cocropping - Yang Zhang; Bao-Ying Wang; Jun Zhang; Ying-Han Liu; Dan-Yao Tang; Jun Zhao; Chuan-Chao Dai (Agriculture, Ecosystems & Environment, 2023)

The sulfate assimilation and reduction of marine microalgae and the regulation of illumination - Wen-Ying Dai; Lu Han; Pei-Feng Li; Qin-Dao Li; Li-Jun Xie; Chun-Ying Liu; Jun-Ru Kong; Ru Jia; Dan-Yang Li; Gui-Peng Yang (Marine Environmental Research, 2023)

Prediction of membrane purification by membrane fouling based on mathematic and machine learning models combined with image processing technology - Lu Wang; Zonghao Li; Jianhua Fan; Guanyu Lu; Dan Liu; Zhiwu Han (Journal of Environmental Chemical Engineering, 2023)

A systemic evaluation of aerobic granular sludge among granulation, operation, storage, and reactivation processes in an SBR - Jun Liu; Xushen Han; Xuewu Zhu; Jun Li; Dan Zhong; Liangliang Wei; Heng Liang (Environmental Research, 2023)

Reversible switchable wettability of intrinsic micro/nanostructured pollen microcarriers via pH-induce from superhydrophobicity to superhydrophilicity - Dan Li; Liwen Sun; Lingjuan Shi; Le Zhuo; Li Yang; Jiayi Zhang; Yaner Han; Tiantian Ye; Shujun Wang (Chemical Engineering Journal, 2023)

Imbalance of multiple neurotransmitter pathways leading to depression-like behavior and cognitive dysfunction in the triple transgenic mouse model of Alzheimer disease - Meng Zhang; Li-yuan Liu; Yong Xu; Wen-zhi Wang; Nian-zhuang Qiu; Fang-fang Zhang; Feng Zhang; Xiao-dan Wang; Wei Chen; Xiao-yan Xu; Yong-feng Gao; Mei-hua Chen; et al. (Metabolic Brain Disease, 2023)

Phosphorus removal potential of aquatic macrophytes in a shallow eutrophic system - Chunqi Shen; Dan Wu; Baoshan Chen; Bahram Khazaei; Chenhua Han (Hydrobiologia, 2023)

Effect of Ginkgo biloba endophytic bacterium Variovorax sp. R1 on the biological control of postharvest cucumber gray mold and related physiological mechanisms - Biying Yang; Zilong Li; Yan Ding; Min Zang; Shuhong Ye; Fengli Han; Dan Chen; Xiaofei Cai (European Journal of Plant Pathology, 2023)

Optimal design of a glider array for the observation of tropical cyclones - Yutong Sun; Dan Cheng; Shaoqiong Yang; Chenyi Luo; Di Tian; Han Zhang; Yanhui Wang (Progress in Oceanography, 2023)

C21 steroids from the roots of Marsdenia tenacissima - Jin-Ling Liu; Hong-Tao Xu; Dan-Dan Mu; Xiao Han; Ting-Ting Du; Yong-li Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

Characterization of a novel nornicotine-degrading strain Mycolicibacterium sp. SMGY-1XX from a nornicotine-degrading consortium and preliminary elucidation of its biodegradation pathway by multi-omics analysis - Bingjun Dang; Wei Jia; Shuanglong Ma; Xiaoping Zhang; Yao Huang; Wuxing Huang; Dan Han; Kai Zhang; Fanchong Zhao; Yuwei Zhang; Zicheng Xu (Journal of Hazardous Materials, 2023)

Transparent, self-adhesive, highly environmental stable, and water-resistant ionogel enabled reliable strain/temperature sensors and underwater communicators - Han Wang; Yanya Mao; Dan Ji; Lei Wang; Lian Wang; Jianwen Chen; Xiaohua Chang; Yutian Zhu (Chemical Engineering Journal, 2023)

The Transcription Regulator GntR/HutC Regulates Biofilm Formation, Motility and Stress Tolerance in Lysobacter capsici X2-3 - Dan Zhao; Jing Wang; Hong Wang; Xiaoping Zhu; Chao Han; Aixin Liu (Current Microbiology, 2023)

Targeting NF-κB pathway by dietary lignans in inflammation: expanding roles of gut microbiota and metabolites - Dan Li; Feijun Luo; Tianyi Guo; Shuai Han; Hanqing Wang; Qinlu Lin (Critical Reviews in Food Science and Nutrition, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Mid-Neoproterozoic tectonic switch from orogeny to intraplate extension in NW Tarim Craton: New evidence from a composite dike of the Aksu Group - Hong-Xiang Wu; Feng-Qi Zhang; Yildirim Dilek; Han-Lin Chen; Kong-Yang Zhu; Xiu-Bin Lin; Qin-Yan Wang; Hong-Dan Deng; Xiao-Gan Cheng (Precambrian Research, 2023)

Rapid nondestructive detecting of wheat varieties and mixing ratio by combining hyperspectral imaging and ensemble learning - Xinna Jiang; Youhua Bu; Lipeng Han; Jianping Tian; Xinjun Hu; Xiaobing Zhang; Dan Huang; Huibo Luo (Food Control, 2023)

Paintable graphene oxide-hybridized soy protein-based biogels for skin radioprotection - Daijun Zhou; Hui Liu; Lu Han; Di Liu; Xiaomei Liu; Qingyan Yan; Dan He; ZhiHui Li; Xiong Lu; Chaoyang Jiang; Dong Li (Chemical Engineering Journal, 2023)

Slow stripe rusting in Chinese wheat Jimai 44 conferred by Yr29 in combination with a major QTL on chromosome arm 6AL - Shengjie Liu; Dan Liu; Chuanliang Zhang; Wenjing Zhang; Xiaoting Wang; Zhiwen Mi; Xin Gao; Yong Ren; Caixia Lan; Xiukun Liu; Zhendong Zhao; Jianjun Liu; et al. (Theoretical and Applied Genetics, 2023)

Sono-enhanced heterogeneous Fenton catalysis: magnetic halloysite nanotube synthesis and accelerated free radical generation - Hongbing Dan; Songlin Han; Yue Gao; Baoyu Gao; Qinyan Yue (Environmental Science and Pollution Research, 2023)

Predicting the interrill erosion rate on hillslopes incorporating soil aggregate stability on the Loess Plateau of China - Ya Liu; Gang Liu; Hai Xiao; Chenxi Dan; Chengbo Shu; Yuqian Han; Qiong Zhang; Zhen Guo; Yang Zhang (Journal of Hydrology, 2023)

Effective adsorption and removal of malachite green and Pb2+ from aqueous samples and fruit juices by pollen–inspired magnetic hydroxyapatite nanoparticles/hydrogel beads - Yuwei Hua; Donghui Xu; Zhongxiao Liu; Jie Zhou; Jiatong Han; Zhihao Lin; Dan Xu; Ge Chen; Xiaodong Huang; Jing Chen; Jun Lv; Guangyang Liu (Journal of Cleaner Production, 2023)

Identify nitrogen transport paths and sources contribution in karst valley depression area using isotopic approach - Meng Lu; Fu-Jun Yue; Xiao-Dan Wang; Zi-Han Liu; Zhi-Yu Shi; Ping Zhang (Journal of Environmental Management, 2023)

Selenium in soil-plant system: Transport, detoxification and bioremediation - Lili Qu; Jiayang Xu; Zhihua Dai; Ali Mohamed Elyamine; Wuxing Huang; Dan Han; Bingjun Dang; Zicheng Xu; Wei Jia (Journal of Hazardous Materials, 2023)

Tannic acid-derived selective capture of bacteria from apple juice - Yi Kang; Min Li; Yaru Han; Hao Sun; Jie Dan; Yanmin Liang; Qiuping Zhang; Zehui Su; Tianli Yue; Jianlong Wang; Wentao Zhang (Food Chemistry, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

Recent advances on the biological activities of purple sweet potato anthocyanins - Chao Tang; Jiaqi Han; Dan Chen; Shuai Zong; Jun Liu; Juan Kan; Chunlu Qian; Changhai Jin (Food Bioscience, 2023)

Complete nitrogen removal from low-strength wastewater via double nitrite shunt coupling anammox and endogenous nitrate respiration: Functional metabolism and electron transport - Qiongpeng Dan; Rui Du; Tong Wang; Tiantian Sun; Honggui Han; Xiaorong Zhu; Xiyao Li; Qiong Zhang; Yongzhen Peng (Chemical Engineering Journal, 2023)

Histone modification landscape and the key significance of H3K27me3 in myocardial ischaemia/reperfusion injury - Le Ni; Bowen Lin; Yanping Zhang; Lingjie Hu; Jianghua Lin; Fengmei Fu; Meiting Shen; Can Li; Lei Chen; Jian Yang; Dan Shi; Yi-Han Chen (Science China Life Sciences, 2023)

RNA-Sequencing Reveals Gene Expression and Pathway Signatures in Umbilical Cord Blood Affected by Birth Delivery Mode - Yongjie Liu; Kun Sun; Yuexin Gan; Han Liu; Juehua Yu; Wei Xu; Lin Zhang; Dan Chen (Phenomics, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Effect of Different Forms of Silicon Application on Wheat Aphid Resistance - Ying Jiang; Xiu-Xiu Qi; Zhong-Hua Wang; Xiao-Dan Liu; Yan-Lai Han; Hui Li; Yi Wang (Agricultural Research, 2023)

Integrated assessment and critical obstacle diagnosis of rural resource and environmental carrying capacity with a social–ecological framework: a case study of Liyang county, Jiangsu Province - Dan Yi; Guanqiao Ding; Yi Han; Jialin Yi; Jie Guo; Minghao Ou (Environmental Science and Pollution Research, 2023)

Two-Stage Learning Model-Based Angle Diversity Method for Underwater Acoustic Array - Yu Zhang; Dan Zhang; Zhen Han; Peng Jiang (Marine Geodesy, 2023)

Comparison study of different forward modeling approaches by using the finite-element method for 3D magnetotelluric data in anisotropic media - Ningbo Bai; Bo Han; Xiangyun Hu; Junjun Zhou; Dan Zhu (Physics of the Earth and Planetary Interiors, 2023)

Revealing the potential of organo-mineral complexes in agricultural application using bibliometrics - Xuehao Zheng; Belay Tafa Oba; Han Wang; Bin Zhang; Chengqiang Shu; Yan Song; Jianfeng Fu; Shejiang Liu; Yuxin Zhang; Nan Dai; Dan Song; Hui Ding (Journal of Cleaner Production, 2023)

Preparation, characterization and safety evaluation of Ligusticum chuanxiong essential oils liposomes for treatment of cerebral ischemia-reperfusion injury - Yu Long; Shuang Yu; Dan Li; Ai Shi; Yin Ma; Jie Deng; Xiao-qiu Li; Jing Wen; Yuan-yuan Wu; Yue Hu; Xiao-fang He; Nan Li; et al. (Food and Chemical Toxicology, 2023)

Inhibiting N2O emissions and improving environmental benefits by integrating garlic growing in grain production systems - Dan Liu; Hongwei Dong; Chi Ma; Qin Mo; Bo Liu; Ahmad Irshad; Hui Li; Baoping Yang; RuiXia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (Agriculture, Ecosystems & Environment, 2023)

Calculation Model of Vertical Bearing Capacity of Rock-Embedded Piles Based on the Softening of Pile Side Friction Resistance - Erdi Abi; Li Shen; Mingwei Liu; Hongbo Du; Dan Shu; Yafeng Han (Journal of Marine Science and Engineering, 2023)
Rock-socketed pile is widely used in coastal wharf, Marine bridge, and Marine power engineering, and the end bearing function is considered more in the design process. However, the lateral friction resistance of rock-socketed piles is an important bearing part, and the load transfer mechanism of the pile–soft rock interface is an important research focus. In this paper, a comparative analysis was adopted in the test, and ten groups of test specimens were made, including five groups of natural and saturated mudstone specimens, respectively. The characteristics of interfacial load transfer were analyzed through the shear test of a pile–mudstone interface. A calculation model for the vertical bearing capacity of rock-socketed piles based on the softening of lateral friction resistance was established, and the effects of interface relative displacement, lateral positive pressure, pile length, and pile stiffness on the vertical bearing capacity of rock-socketed piles were analyzed. The results show that the shear strength of the pile–rock interface is lower than that of the mudstone interface, and the interfacial shear strength shows the characteristics of “first increasing, then decreasing, and finally flattening with the increase of shear displacement”. The vertical ultimate bearing capacity and residual bearing capacity under saturation were 89.49% and 89.73% of the natural state, respectively. With the increase of pile side pressure, the proportion of pile side friction resistance increased by 39.96%, and the pile side friction resistance was fully exerted. With the increase of pile length, the vertical ultimate bearing capacity of pile foundation increased, and the residual bearing capacity change value increased from 6.80% to 16.97%. However, the increase in pile stiffness had little effect on the vertical bearing capacity. The calculation model can provide a certain reference for the design and calculation of rock-socketed piles in soft rock areas.

A new insight into the low membrane fouling tendency of liquid-liquid hollow fiber membrane contactor capturing ammonia from human urine - Junhui Zhang; Kuiling Li; Mengfei Xie; Qi Han; Li Feng; Dan Qu; Liqiu Zhang; Ke Wang (Water Research, 2023)

Surrogate models for twin-VAWT performance based on Kriging and artificial neural networks - Yaoran Chen; Dan Zhang; Xiaowei Li; Yan Peng; Xiangyu Zhang; Zhaolong Han; Yong Cao; Zhikun Dong (Ocean Engineering, 2023)

Proteomic analysis reveals differential responsive mechanisms in Solanum nigrum exposed to low and high dose of cadmium - Ling-Yu Song; Xiang Liu; Lu-Dan Zhang; Wen-Jun Hu; Chao-Qun Xu; Jing Li; Shi-Wei Song; Ze-Jun Guo; Chen-Yang Sun; Han-Chen Tang; Ji-Cheng Wang; Xue-Yi Zhu; et al. (Journal of Hazardous Materials, 2023)

Urinary concentrations of organophosphate esters in relation to semen quality: A cross-sectional study - Yaping Li; Dan Luo; Xiaoya Zhao; Han Wang; Zhiyi Zheng; Jun Liu; Chong Liu; Hui Wang; Yingjun Chen; Yinzhu Shang; Wenqing Lu; Surong Mei; et al. (Science of The Total Environment, 2023)

Exploring the relationship between deep roots and shoot growth of wheat under different soil moisture: A large soil column experiment 1 - Dan Liu; Siwei Mou; Yufeng Zou; Baoping Yang; Ruixia Ding; Junfeng Nie; Xudong Zhang; Zhikuan Jia; Qingfang Han (Rhizosphere, 2023)

Macromolecular structural characteristics and functional potential of tobacco stalk lignin from the phosphotungstic acid-assisted delignification process - Zhichang Liu; Xidong Peng; Yaowei Xu; Tianming Tang; Shuoguo Wei; Ben Liu; Dan Wang; Han-Min Wang; Jungang Jiang (Biomass and Bioenergy, 2023)

Evaluation method of local failure characteristics for joint based on white light scanning technology - Leibo Song; Dan Zhang; Gang Wang; ShiGui Du; Gaojian Hu; Guansheng Han; Xingkai Wang; Xiqi Liu (Natural Hazards, 2023)

Automatic identification of seismic faults via integrating Residual Network-50 residual blocks and convolutional block attention modules - Xin-Wei Wang; Su-Zhen Shi; Xu-Jun Yao; Jin-Bo Pei; Yi-Fan Wang; Han-Bo Yang; Dan-Qing Liu (Applied Geophysics, 2023)

A ratiometric fluorescent biosensing platform for ultrasensitive detection of Salmonella typhimurium via CRISPR/Cas12a and silver nanoclusters - Long Ma; Jiajing Wang; Yaru Li; Dan Liao; Wenlu Zhang; Xiao Han; Shuli Man (Journal of Hazardous Materials, 2023)

Facile electrochemically induced vacancy modulation of NiCo2O4 cathode toward high-performance aqueous Zn-based battery - Yu Zhang; Dan Sun; Yixun Wang; Xiaoqi Liu; Hongman Sun; Tonghui Cai; Xuejin Li; Han Hu; Xiaoyun Zhang; Wei Xing; Zifeng Yan (Chemical Engineering Journal, 2023)

Collateral-Core Ratio as a Novel Predictor of Clinical Outcomes in Acute Ischemic Stroke - Jinhao Lyu; Sa Xiao; Zhihua Meng; Xiaoyan Wu; Wen Chen; Guohua Wang; Qingliang Niu; Xin Li; Yitong Bian; Dan Han; Weiting Guo; Shuai Yang; et al. (Translational Stroke Research, 2023)

Riemerella anatipestifer GldG is necessary for secretion of effectors by type IX secretion system - Zongchao Chen; Wenlong Han; Min Zhu; Dan Liu; Pengfei Niu; Ruyu Shen; Chan Ding; Shengqing Yu (Veterinary Microbiology, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Cross-biome soil viruses as an important reservoir of virulence genes - Li Bi; Li-Li Han; Shuai Du; Dan-Ting Yu; Ji-Zheng He; Li-Mei Zhang; Hang-Wei Hu (Journal of Hazardous Materials, 2023)

A 3D smart wood membrane with high flux and efficiency for separation of stabilized oil/water emulsions - Jianfei Wu; Ziwei Cui; Yang Yu; He Han; Dan Tian; Jundie Hu; Jiafu Qu; Yahui Cai; Jianlin Luo; Jianzhang Li (Journal of Hazardous Materials, 2023)

Nutrient dynamics and microbial community response in macrophyte-dominated lakes: Implications for improved restoration strategies - Shuai Ma; Huanhuan Geng; Changchun Yan; Xiaomin Han; Dan Xu; Furong Zhao; Ruth E. Blake; Beihai Zhou; Huilun Chen; Rongfang Yuan; Baoshi Jin; Haijun Liu; et al. (Journal of Environmental Management, 2023)

A high-efficient and stable artificial superoxide dismutase based on functionalized melanin nanoparticles from cuttlefish ink for food preservation - Yanmin Liang; Yaru Han; Jie Dan; Runli Li; Hao Sun; Jianlong Wang; Wentao Zhang (Food Research International, 2023)

Environmental, economic, and energy analysis of municipal solid waste incineration under anoxic environment in Tibet Plateau - Zeng Dan; Yuechi Che; Xutong Wang; Peng Zhou; Zhiyong Han; Duo Bu; Xuebin Lu; Wenchao Ma; Guanyi Chen (Environmental Research, 2023)

Forecasting and analysis of the effect of lifestyle on cognitive dysfunction induced by occupational aluminum exposure based on Bayesian networks - Dan Zhao; Xiao Han; Jiaping Huan; Dan Gao; Tianshu Wang; Jing Song; Linping Wang; Huifang Zhang; Tiane Luo; Baolong Pan; Qiao Niu; Xiaoting Lu (Environmental Toxicology and Pharmacology, 2023)

Hierarchically porous zirconium-based metal–organic frameworks for rapid adsorption and enrichment of sulfonamide antibiotics - Lizhen Han; Peige Qin; Mengyuan Li; Dan Li; Mengyao Mu; Yanmei Gao; Shiping Zhu; Minghua Lu; Zongwei Cai (Chemical Engineering Journal, 2023)

Sn2P2S6: A lead-free reversible thermochromic ferroelectric with high near-infrared reflectance - Meixia Wu; Xiao Zhou; Xihui Liang; Yifeng Han; Yonghong Li; Xingan Jiang; Xueyun Wang; Yisheng Chai; Xiang Zhou; Hui Yang; Dan Lin; Ping Xu; et al. (Chemical Engineering Journal, 2023)

N-type small molecule electron transport materials with D-A-D conjugated core for non-fullerene organic solar cells - Dan Zhou; Yubing Li; Hehui Zhang; Haolan Zheng; Xingxing Shen; Wen You; Lin Hu; Liangjing Han; Yongfen Tong; Lie Chen (Chemical Engineering Journal, 2023)

The Detection and Imaging of pH Values in Living Cells with Hemicyanine Based Colorimetric Mitochondria-Targeted Fluorescent Probe - Zhengcheng Chen; Dan Wu; Han Yang; Ping Zou; Guangtu Wang (Journal of Fluorescence, 2023)

Assimilation of Ocean Surface Wind Data by the HY-2B Satellite in GRAPES: Impacts on Analyses and Forecasts - Jincheng Wang; Xingwei Jiang; Xueshun Shen; Youguang Zhang; Xiaomin Wan; Wei Han; Dan Wang (Advances in Atmospheric Sciences, 2023)

Estimating fractional cover of saltmarsh vegetation species in coastal wetlands in the Yellow River Delta, China using ensemble learning model - Zhanpeng Wang; Yinghai Ke; Dan Lu; Zhaojun Zhuo; Qingqing Zhou; Yue Han; Peiyu Sun; Zhaoning Gong; Demin Zhou (Frontiers in Marine Science, 2022)
Saltmarshes in coastal wetlands provide important ecosystem services. Satellite remote sensing has been widely used for mapping and classification of saltmarsh vegetation, however, medium-spatial-resolution satellite datasets such as Landsat-series imagery may induce mixed pixel problems over saltmarsh landscapes which are spatially heterogeneous. Sub-pixel fractional cover estimation of saltmarsh vegetation at species level are required to better understand the distribution and canopy structure of saltmarsh vegetation. In this study, we presented an approach framework for estimating and mapping the fractional cover of major saltmarsh species in the Yellow River Delta, China based on time series Landsat 8 Operational Land Imager data. To solve the problem that the coastal area is frequently covered by clouds, we adopted the recently developed virtual image-based cloud removal (VICR) algorithm to reconstruct missing image values under the cloud/cloud shadows over the time series Landsat imagery. Then, we developed an ensemble learning model (ELM), which incorporates Random Forest Regression (RFR), K-Nearest Neighbor Regression (KNNR) and Gradient Boosted Regression Tree (GBRT) based on temporal-spectral features derived from the time-series cloudless images to estimate the fractional cover of major vegetation types, i.e., Phragmites australis , Suaeda salsa and the invasive species, Spartina alterniflora . High spatial resolution imagery acquired by the Unmanned Aerial Vehicle and Gaofen-6 satellites were used for reference sample collections. The results showed that our approach successfully estimated the fractional cover of each saltmarsh species (average of R-square:0.891, RMSE: 7.48%). Through four scenarios of experiments, we found that the ELM is advantageous over each individual model. When the images during key months were absent, cloud removal for the Landsat images considerably improved the estimation accuracies. In the study area, Spartina alterniflora covers the largest area (5753.97 ha), followed by Phragmites australis with spatial extent area of 4208.4 ha and Suaeda salsa of 1984.41 ha. The average fractional cover of S. alterniflora was 58.45%, that of P. australis was 51.64% and that of S.salsa was 51.64%.

Plant diversity is coupled with soil fungal diversity in a natural temperate steppe of northeastern China - Dan Liu; Guohua Liu; Li Chen; Wangya Han; Dongbo Wang (Soil Ecology Letters, 2022)

Effects of ridge planting on crop seedlings under saline water drip irrigation - Xiaoyu Han; Yaohu Kang; Shuqin Wan; Dan Li (Irrigation and Drainage, 2022)
A field experiment was conducted in northwest China to study the effects of different irrigation water salinity levels on the emergence and growth of corn, sunflower, summer squash, and cowpea. Two tillage systems (flat and ridge planting) and five salinity levels (at 1.7, 4.0, 6.3, 8.6, and 10.9 dS/m) were tested. Compared with flat planting, the soil salinity within 30 cm horizontally from the drip tapes decreased by 15% in the ridge planting system. Ridge planting significantly improved the emergence and growth of crops, which was mainly manifested in higher emergence rates, reduced emergence time, and increased dry biomass, especially under high‐salinity conditions (electrical conductivity of irrigation water >4 dS/m). The electrolytic conductivity of the saturation extract threshold at which corn, sunflower, summer squash, and cowpea endured without reduced emergence rates was 5.8, 5.8, 4.8, and 4.0 dS/m, respectively. Above this threshold, the relative emergence rate decreased by 11%, 16%, 14%, and 20%, respectively. Our results indicate the agronomic benefits of ridge planting, and the soil environment was improved by ridge planting with saline water drip irrigation. In addition, we discuss the crop responses in terms of emergence rates and relative seedling dry biomass in relation to soil salinity. Suggestions for the secure and efficient use of saline water for irrigation in arid regions have been put forward.

The effect of reservoir expansion from underground karst cave to surface reservoir on water quality in southwestern China - Meng Lu; Xiao-Dan Wang; Fu-Jun Yue; Zi-Han Liu; Zhi-Yu Shi; Ping Zhang (Environmental Science and Pollution Research, 2022)

Brevilaterin B from Brevibacillus laterosporus has selective antitumor activity and induces apoptosis in epidermal cancer - Zhou Chen; Lulu Wang; Yangliu Liu; Panpan Han; Dan Hong; Siting Li; Aijin Ma; Yingmin Jia (World Journal of Microbiology and Biotechnology, 2022)

EST-SSR marker-based investigation on genetic diversity and genetic structure of Juglans mandshurica Maxim. in Shandong Province of China - Zihao Wang; Hao Zhang; Boqiang Tong; Biao Han; Dan Liu; Ping Zhang; Dechang Hu (Genetic Resources and Crop Evolution, 2022)

Decadal Changes in the Annual Growth of Two Commercial Ommastrephid Species in the Pacific Ocean - Peiwu Han; Jianhua Li; Yating Dan; Bilin Liu; Xinjun Chen; Zhou Fang (Fishes, 2022)
Neon flying squid Ommastrephes bartramii and jumbo flying squid Dosidicus gigas are two important commercial ommastrephid species in the Pacific Ocean. As short-lived marine species, squids are highly susceptible to changes in climate and marine environments. According to samples collected from the northwest and southeast Pacific Ocean in different years, we explored the growth characteristics of these two squids in terms of their mantle length (ML) distribution and the relationship between mantle length and body weight (LWR), also considering the relative condition factors (Kn), and explored the effects of the El Niño and Southern Oscillation (ENSO) on their growth. The results showed that the ML for O. bartramii and D. gigas had significant differences among different years and different sexes (p 3), and parameters a and b were influenced by year and sex. Furthermore, there were significant differences in Kn in both squids for different years and different sexes (p

Cytokine storm and targeted therapy in hemophagocytic lymphohistiocytosis - Han-qi Zhang; Si-Wei Yang; Yi-Cheng Fu; Ming-Cong Chen; Cheng-Hao Yang; Ming-Hua Yang; Xiao-Dan Liu; Qing-Nan He; Hua Jiang; Ming-Yi Zhao (Immunologic Research, 2022)

A Carrier phase tracking method for vector tracking loops - Zhifeng Han; Dan Liu; Zhaokun Wei; Ying Xu; Rongbing Li (GPS Solutions, 2022)

Degradation mechanism of BPA under VUV irradiation: efficiency contribution and DFT calculations - Ting-Ting Cao; Han Cui; Dan-Dan Zhou; Xin Ren; Chong-Wei Cui (Environmental Science and Pollution Research, 2022)

Relative reinforcing effects of dibutylone, ethylone, and N-ethylpentylone: self-administration and behavioral economics analysis in rats - Miaojun Lai; Dan Fu; Zeming Xu; Han Du; Huifen Liu; Youmei Wang; Peng Xu; Wenhua Zhou (Psychopharmacology, 2022)

Feasibility Studies of Nebulized SARS-CoV-2 Neutralizing Antibody in Mice and Cynomolgus Monkeys - Jilei Jia; Zhaojuan Yin; Xiao Zhang; Huimin Li; Dan Meng; Qianqian Liu; Hongfang Wang; Meng Han; Shixiang Suo; Yan Liu; Ping Hu; Chunyun Sun; et al. (Pharmaceutical Research, 2022)
Purpose Neutralizing antibodies, administrated through intravenous infusion, have shown to be highly efficacious in treating mild and moderate COVID-19 caused by SARS-CoV-2 infection in the lung. However, antibodies do not transport across the plasma-lung barrier efficiently, and up to 100 mg/kg dose was used in human causing significant supply and cost burdens. This study was to explore the feasibility of nebulized antibodies inhalation delivery as an alternative route. Methods HB27, a potent RBD-specific humanized monoclonal antibody (Zhu et al. in National Sci Rev. 8:nwaa297, 2020), showed excellent protection against SARS-CoV-2 in animal model and good safety profile in clinical studies. The pharmacokinetics and preliminary safety of HB27 administrated through the respiratory tract were studied in mice and cynomolgus monkeys here. Results At a single 5 mg/kg dose, the peak HB27 concentration in mice pulmonary epithelial lining fluid (ELF) reached 857.8 μg/mL, 670-fold higher than the PRNT 90 value of 1.28 μg/mL, and maintained above PRNT 90 over 240 h. In contrast, when administrated by intravenous injection at a 5 mg/kg dose, the antibody concentrations in mice ELF were below PRNT 90 value throughout, and were about 50-fold lower than that in the serum. In cynomolgus monkeys administrated with a single dose through inhalation, the antibody concentration in ELF remained high within 3 days. No drug-related safety concerns were observed in the studies. Conclusions The study demonstrated that nebulized neutralizing antibody delivery though inhalation could be a more efficient and efficacious alternative approach for treating COVID-19 and other respiratory infectious diseases, and warrants further evaluation in clinical studies.

Identification and QTL mapping of important agronomic traits based on rice short-wide grain CSSL-Z752 with restorer line Xihui 18 as background - Lin-Jun Cai; Han Yun; Xiao-Long Zhong; Dan Du; Xi-Man Peng; Ji-Chao Dai; Zhen-Lin Yang; Fang-Ming Zhao; Chang-Wei Zhang (Cereal Research Communications, 2022)

Rhizobium quercicola sp. nov., isolated from the leaf of Quercus variablis in China - Cheng-Bin Wang; Dan-Ran Bian; Ning Jiang; Han Xue; Chun-Gen Piao; Yong Li (Archives of Microbiology, 2022)

Life cycle assessment of auto-tropically cultivated economic microalgae for final products such as food, total fatty acids, and bio-oil - Dan Zhang; Siyuan An; Rao Yao; Wen Fu; Yujie Han; Ming Du; Zixi Chen; Anping Lei; Jiangxin Wang (Frontiers in Marine Science, 2022)
Life cycle assessment (LCA) is a powerful tool to evaluate environmentally sustainable production or consumption of various goods or services. Microalgae are single-celled green factories and good resources of biofuels, bioactive products, food ingredients, and degradable biomaterials. Currently, microalgae are also valuable for mitigating elevated greenhouse gases like CO 2 levels and treatment of wastewater. LCA evaluation was limited and separated, majorly in microalgal biofuels and heterotrophic cultivation. Comparative LCA for different final algal products such as algal powder, bio-oil, total fatty acid, and residue recycling is still limited, especially autotrophic algal cultivation for products other than bio-oils and biofuels. Thus, we chose several autotrophic cultivated microalgae and made a comparative LCA among these selected species and a detailed step-by-step production in Chlorella sp. Results indicated that we could significantly reduce the production cost and lower environmental impacts by selecting algal species and final products, optimizing methods for algal cultivation, biomass separation, and drying process, and land selection plus electricity renewable energy, together with thermal power plants nearby for CO 2 or flu gas. It shed light on the insight of microalgal consumption selection under current international requirements and challenges for carbon sequestration.

Pore development in terrestrial shale reservoirs: the Permian Lucaogou Formation, Junggar Basin, northwestern China - Y. Jin; J. Tian; C. Han; H. Liu; L. Dong; S. Dan (Australian Journal of Earth Sciences, 2022)

Inhibition of visfatin alleviates sepsis-induced intestinal damage by inhibiting Hippo signaling pathway - Zhong-Shen Kuang; Yu-Xin Leng; Ning Yang; Zheng-Qian Li; Ya-Nan Zong; Deng-Yang Han; Yue Li; Jin-Dan He; Xing-Ning Mi; Zhu-Kai Cong; Xi Zhu; Chang-Yi Wu; et al. (Inflammation Research, 2022)
Background The aim of this study is to investigate role of Visfatin, one of the pro-inflammatory adipokines, in sepsis-induced intestinal injury and to clarify the potential mechanism. Methods C57BL/6 mice underwent cecal ligation and puncture (CLP) surgery to establish sepsis model in vivo. Intestinal epithelial cells were stimulated with LPS to mimic sepsis-induced intestinal injury in vitro. FK866 (the inhibitor of Visfatin) with or without XMU-MP-1 (the inhibitor of Hippo signaling) was applied for treatment. The expression levels of Visfatin, NF-κB and Hippo signaling pathways-related proteins were detected by western blot or immunohistochemistry. The intestinal cell apoptosis and intestinal injury were investigated by TUNEL staining and H&E staining, respectively. ELISA was used to determine the production of inflammatory cytokines. Results The expression of Visfatin increased in CLP mice. FK866 reduced intestinal pathological injury, inflammatory cytokines production, and intestinal cell apoptosis in sepsis mice. Meanwhile, FK866 affected NF-κB and Hippo signaling pathways. Additionally, the effects of FK866 on inflammatory response, apoptosis, Hippo signaling and NF-κB signaling were partly abolished by XMU-MP-1, the inhibitor of Hippo signaling. In vitro experiments also revealed that FK866 exhibited a protective role against LPS-induced inflammatory response and apoptosis in intestinal cells, as well as regulating NF-κB and Hippo signaling, whereas addition of XMU-MP-1 weakened the protective effects of FK866. Conclusion In short, this study demonstrated that inhibition of Visfatin might alleviate sepsis-induced intestinal injury through Hippo signaling pathway, supporting a further research on Visfatin as a therapeutic target.

Noise suppression of distributed acoustic sensing vertical seismic profile data based on time–frequency analysis - Dan Shao; Tonglin Li; Liguo Han; Yue Li (Acta Geophysica, 2022)

Two new 2,5-diketopiperazine derivatives from mangrove-derived endophytic fungus Nigrospora camelliae-sinensis S30 - Dan-Yu Huang; Xu-Hua Nong; Yu-Qin Zhang; Wei Xu; Long-Yu Sun; Tao Zhang; Guang-Ying Chen; Chang-Ri Han (Natural Product Research, 2022)

Roseicella aquatilis sp. nov., isolated from freshwater lake - Dan-Dan Zhang; Ya-Nan Zhao; Rui-Han He; Yu-Qi Yan; Zong-Jun Du (Archives of Microbiology, 2022)

Ligustilide ameliorates cognitive impairment via AMPK/SIRT1 pathway in vascular dementia rat - Dong Peng; Han-Zi Qiao; Hong-Yu Tan; Yi-Xue Wang; Dan Luo; Li-Jun Qiao; Ye-Feng Cai; Shi-Jie Zhang; Qi Wang; Li Guan (Metabolic Brain Disease, 2022)

Fine mapping and phenotype assessment of the novel lesion mimic and early senescence lmes5 mutant in rice - Han Yun; Linjun Cai; Dan Du; Yunxia Guo; Hang Sun; Xiaolong Zhong; Ximan Peng; Jichao Dai; Changwei Zhang (Euphytica, 2022)

Increased expression of HMGB1 in the implantation phase endometrium is related to recurrent implantation failure - Mi Han; Yi Cao; Wenjie Zhou; Mingjuan Zhou; Xiaowei Zhou; Dan Zhang; Bufang Xu; Aijun Zhang (Molecular Biology Reports, 2022)

Characterization and clinical relevance of PDGFRA pathway copy number variation gains across human cancers - Lizhu Liu; Lihong Wu; Dan Shan; Bo Han (Molecular Genetics and Genomics, 2022)
We investigated the copy number variation (CNV) of PDGFRA pathway across all common cancer types as well as its clinical relevance. This study included a total of 10,678 patients with pan-cancerous species involving 33 types of cancers and patient information was obtained from The Cancer Genome Atlas. According to the PDGFRA pathway CNV, all samples were divided into copy number gain (CN gain) group and No CN gain group. The analysis of loss of heterozygosity (LOH) fraction, CNV burden, tumor mutation burden (TMB), and the number of immunogenic mutations were performed, as well as the correlation analysis of PDGFRA pathway CN gain with tumor-related signaling pathways and tumor-infiltrating immune cell subpopulations. The results showed that CN gain of PDGFRA pathway in the cancer patients was associated with significantly shorter overall survival. The CN gain of PDGFRA pathway was identified as a prognostic risk factor for some tumors. CN gain was accompanied by an altered percentage of LOH, CNV burden, TMB, the number of immunogenic mutations were increased and tumor-infiltrating immune cell subpopulations were less. While certain tumor-related signaling pathways, such as hypoxia, cell cycle, DNA repair, and epithelial-mesenchymal transition were more enriched in the CN gain group, quiescence, and inflammation pathways were more enriched in the No CN gain group. In conclusion, PDGFRA pathway CNV gain may be a poor prognostic factor in cancer patients.

Field investigation and numerical simulation on rockfalls in Zhangmu Town, Tibet, China - Zhong-fu Wang; Han-dong Liu; Si-ming He; Dan Bi (Journal of Mountain Science, 2022)

Effects of ambient fine particulate matter on oxidative stress, inflammation, and janus kinase/signal transducer and activator of transcription signal molecules: a panel study of asthmatic adults in Taiyuan, China - Nannan Liu; Xiaoyan Ma; Jing Wang; Liangpo Liu; Hong Geng; Bianzhuan Yang; Jianbiao Han; Jiayu Tian; Xin Wang; Caihong Wang; Dan Wang; Hao Shi; et al. (Air Quality, Atmosphere & Health, 2022)

Rapid visual detection of Micropterus salmoides rhabdovirus using recombinase polymerase amplification combined with lateral flow dipsticks - Zizhao Feng; Xin Chu; Minzhen Han; Chenwei Yu; Yousheng Jiang; Hao Wang; Liqun Lu; Dan Xu (Journal of Fish Diseases, 2022)
Largemouth bass ( Micropterus salmoides ) is an important freshwater‐cultured species in China. Recently, a lethal and epidemic disease caused by Micropterus salmoides rhabdovirus (MSRV) results in huge economic losses to the largemouth bass industry. Current diagnostics for detecting MSRV are limited in sensitivity and speed and are inconvenient to be used for non‐laboratory detection. In this study, three rapid and convenient detection assays of MSRV by recombinase polymerase amplification (RPA) and lateral flow dipsticks (LFD), targeting the conserved sequences of the MSRV‐SS N gene, are described. With these RPA methods, the detection could achieve within 50 min at 38°C. Both methods of RPA‐AGE and RPA‐LFD could detect the viral DNA as low as 170 copies/μl of the MSRV standard plasmid and were 100‐fold more sensitive than that in the method of routine PCR. Meanwhile, these RPA methods were highly specific for the detection of MSRV and can be feasibly applied to the diagnostic of MSRV infection. In brief, RPA‐AGE, RPA‐LFD and RT‐RPA‐LFD provide convenient, rapid, sensitive and reliable methods that could improve field diagnosis of MSRV with limited machine resources, and would enhance the production of largemouth bass.

Characterization of municipal solid waste incineration and flue gas emission under anoxic environment in Tibet Plateau - Zeng Dan; Wenwu Zhou; Peng Zhou; Yuechi Che; Zhiyong Han; A Qiong; Bu Duo; Xuebin Lv; Qiongda Zhuoma; Jing Wang; Wang Yang; Guanyi Chen (Environmental Science and Pollution Research, 2022)

Correction to: Toward a phylogeny and biogeography of Diaphanosoma (Crustacea: Cladocera) - Henri J. Dumont; Bo-Ping Han; Fei Fei Guo; Hua Chen; Dan Cheng; Ping Liu; Lei Xu; La-Orsri Sanoamuang; Arnola C. Rietzler; Shaolin Xu; Andy Vierstraete; Manuel Elias-Gutierrez (Aquatic Ecology, 2021)

Toward a phylogeny and biogeography of Diaphanosoma (Crustacea: Cladocera) - Henri J. Dumont; Bo-Ping Han; Fei Fei Guo; Hua Chen; Dan Cheng; Ping Liu; Lei Xu; La-Orsri Sanoamuang; Arnola C. Rietzler; Shaolin Xu; Andy Vierstraete; Manuel Elias-Gutierrez (Aquatic Ecology, 2021)

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

TLR2 Potentiates SR-Marco-Mediated Neuroinflammation by Interacting with the SRCR Domain - Lu Wang; Han-Yu Yang; Cai-Xia Zang; Jun-Mei Shang; Hui Liu; Zi-Hong Zhang; Fang-Yu Yuan; Cheng Ju; Fang-Yuan Li; Xiu-Qi Bao; Dan Zhang (Molecular Neurobiology, 2021)

Optimization of hydrothermal synthesis of hydroxyapatite from chicken eggshell waste for effective adsorption of aqueous Pb(II) - Dezhi Shi; Haihang Tong; Mengying Lv; Dan Luo; Pan Wang; Xiaoyi Xu; Zhiyong Han (Environmental Science and Pollution Research, 2021)

Association of myostatin deficiency with collagen related disease-umbilical hernia and tippy toe standing in pigs - Hyo-Jin Paek; Zhao-Bo Luo; Hak-Myong Choe; Biao-Hu Quan; Kai Gao; Sheng-Zhong Han; Zhou-Yan Li; Jin-Dan Kang; Xi-Jun Yin (Transgenic Research, 2021)

Folate metabolizing gene polymorphisms and genetic vulnerability to preterm birth in Korean women - Bit Na Kwon; Noo Ri Lee; Hyung Jun Kim; Yun Dan Kang; Jong Soo Kim; Jin Wan Park; Han Jun Jin (Genes & Genomics, 2021)

Affinibrenneria salicis gen. nov. sp. nov. isolated from Salix matsudana bark canker - Dan-ran Bian; Han Xue; Guang-ming Wang; Chun-gen Piao; Yong Li (Archives of Microbiology, 2021)

Microbially Induced Carbonate Precipitation Techniques for the Remediation of Heavy Metal and Trace Element–Polluted Soils and Water - Xue Chen; Dan Zhang; Steven L. Larson; John H. Ballard; Heather M. Knotek-Smith; Jing Nie; Nan Hu; Dexin Ding; Fengxiang X. Han (Water, Air, & Soil Pollution, 2021)

Cladosporine A, a new indole diterpenoid alkaloid with antimicrobial activities from Cladosporium sp. - Xue Han; Xue-Feng Bao; Chuan-Xi Wang; Jun Xie; Xiao-Jun Song; Ping Dai; Guo-Dong Chen; Dan Hu; Xin-Sheng Yao; Hao Gao (Natural Product Research, 2021)

Persistence, mobility, and leaching risk of flumioxazin in four Chinese soils - Ye Chen; Jiahua Han; Dan Chen; Zhengyi Liu; Kankan Zhang; Deyu Hu (Journal of Soils and Sediments, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Greenhouse gas emissions from semi-aerobic bioreactor landfills with different vent-pipe diameters - Guobin Jiang; Dan Liu; Weiming Chen; Zhiyong Han; Qibin Li (Environmental Science and Pollution Research, 2021)

Bioinformatics analysis of WRKY transcription factors in grape and their potential roles prediction in sugar and abscisic acid signaling pathway - Ting Huang; Jinli Yang; Dan Yu; Xiaoyu Han; Xiuqin Wang (Journal of Plant Biochemistry and Biotechnology, 2021)

Tyrosine kinase Fyn promotes apoptosis after intracerebral hemorrhage in rats by activating Drp1 signaling - Li Zhang; Lu Wang; Han Xiao; Hui Gan; Hui Chen; Shuyue Zheng; Dan Jian; Xuan Zhai; Ning Jiang; Zhao Jing; Ping Liang (Journal of Molecular Medicine, 2021)

Construction of a new plant expression vector and the development of maize germplasm expressing the Aspergillus ficuum phytase gene PhyA2 - Peng Jiao; Wen-Ya Yuan; Han-Dan Zhao; Jing Qu; Pi-Wu Wang; Shu-Yan Guan; Yi-Yong Ma (Genetic Resources and Crop Evolution, 2021)
Phytases, which belong to a special category of orthophosphoric monoester phosphohydrolases, degrade inositol hexaphosphate to produce lower-grade inositol phosphate derivatives and inorganic phosphate. Thus, phytases may improve phosphorus utilization, eliminate the anti-nutrient properties of phytic acid, and mitigate environmental pollution due to phosphorus contamination. In this study, we constructed a new root-specific expression vector by inserting the Aspergillus ficuum phytase gene PhyA2 into pCAMBIA3301-ZmGLU1P-Nos. The subsequent molecular analysis confirmed that six T 4 generation transgenic plants carried and expressed PhyA2 . A quantitative real-time PCR analysis indicated PhyA2 was highly expressed in the transgenic roots. Additionally, the phytase activity was 10.9-fold higher in the transgenic roots (peak activity of 5.432 U/g) than in the control roots. Moreover, compared with the control rhizosphere, the organic phosphorus content in the rhizosphere of the transgenic plants decreased significantly (by up to 5.21 mg/kg). An agronomic trait analysis indicated that PhyA2 expression can increase maize seed weight by up to 25.8 g. Therefore, the integration of PhyA2 into the maize genome can enhance the ability of maize plants to use the phosphorus compounds in soil, while also improving the plant growth status and increasing the seed yield.

Nrf2 deficiency aggravates the kidney injury induced by subacute cadmium exposure in mice - Chengjie Chen; Xue Han; Gang Wang; Dan Liu; Lina Bao; Congcong Jiao; Junjun Luan; Yongyong Hou; Yuanyuan Xu; Huihui Wang; Qiang Zhang; Hua Zhou; et al. (Archives of Toxicology, 2021)

Compound heterozygous mutation of the ASXL3 gene causes autosomal recessive congenital heart disease - Fang Fu; Ru Li; Ting-ying Lei; Dan Wang; Xin Yang; Jin Han; Min Pan; Li Zhen; Jian Li; Fa-tao Li; Xiang-yi Jing; Dong-zhi Li; et al. (Human Genetics, 2021)

Diversity and potential biogeochemical impacts of viruses in bulk and rhizosphere soils - Li Bi; Dan‐Ting Yu; Shuai Du; Li‐Mei Zhang; Li‐Yu Zhang; Chuan‐Fa Wu; Chao Xiong; Li‐Li Han; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Viruses can affect microbial dynamics, metabolism and biogeochemical cycles in aquatic ecosystems. However, viral diversity and functions in agricultural soils are poorly known, especially in the rhizosphere. We used virome analysis of eight rhizosphere and bulk soils to study viral diversity and potential biogeochemical impacts in an agro‐ecosystem. The order Caudovirales was the predominant viral type in agricultural soils, with Siphoviridae being the most abundant family. Phylogenetic analysis of the terminase large subunit of Caudovirales identified high viral diversity and three novel groups. Viral community composition differed significantly between bulk and rhizosphere soils. Soil pH was the main environmental driver of the viral community structure. Remarkably, abundant auxiliary carbohydrate‐active enzyme (CAZyme) genes were detected in viromes, including glycoside hydrolases, carbohydrate esterases and carbohydrate‐binding modules. These results demonstrate that virus‐encoded putative auxiliary metabolic genes or metabolic genes that may change bacterial metabolism and indirectly contribute to biogeochemical cycling, especially carbon cycling, in agricultural soil.

Circulating sortilin levels are associated with inflammation in patients with moyamoya disease - Wenxiu Han; Yi Qiao; Hailiang Zhang; Chunmei Geng; Xing Zhu; Dehua Liao; Yujin Guo; Mengqi Yang; Dan Chen; Pei Jiang (Metabolic Brain Disease, 2021)

Critical roles of macrophages in pressure overload-induced cardiac remodeling - Dan Yang; Han-Qing Liu; Fang-Yuan Liu; Nan Tang; Zhen Guo; Shu-Qing Ma; Peng An; Ming-Yu Wang; Hai-Ming Wu; Zheng Yang; Di Fan; Qi-Zhu Tang (Journal of Molecular Medicine, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Two new compounds from the marine sponge derived fungus Penicillium chrysogenum - Xiao Han; Pinglin Li; Xiangchao Luo; Dan Qiao; Xuli Tang; Guoqiang Li (Natural Product Research, 2020)

Elevated IL-22 in psoriasis plays an anti-apoptotic role in keratinocytes through mediating Bcl-xL/Bax - Bo Wang; Dan Han; Fei Li; Weikun Hou; Lijuan Wang; Liesu Meng; Kuanhou Mou; Shemin Lu; Wenhua Zhu; Yan Zhou (Apoptosis, 2020)
IL-22 is known to mediate inflammation in psoriasis, while IL-22 binding protein (IL-22BP) binds IL-22 to suppress IL-22 signaling. However, the function of IL-22 in regulating apoptosis in psoriasis remains poorly understood. In this study, we found that IL-22/IL-22R1 in lesional skin and IL-22 in serum from psoriatic patients were highly upregulated compared with healthy controls, while IL-22BP was not changed. Correlations between IL-22/IL-22R1 levels and the thickness of psoriatic lesions suggested that IL-22 might positively regulate abnormal hyperplasia in psoriasis. Apoptotic keratinocytes were increased only in stratum corneum, but not in spinous and basal layers of psoriasis. Moreover, IL-22 promoted cell viability in human epidermal keratinocytes (HEKs). The apoptosis induced by TNF-α and IFN-γ was inhibited in HEKs treated with IL-22, since that IL-22 upregulated Bcl-xL and downregulated Bax production in HEKs in the presence of TNF-α and IFN-γ. In addition, IL-22BP could counteract the anti-apoptotic effect of IL-22. Our finding demonstrates that IL-22 might play an anti-apoptosis role on keratinocytes to balance cell proliferation and apoptosis in psoriatic epidermis.

Stenotrophomonas cyclobalanopsidis sp. nov., isolated from the leaf spot disease of Cyclobalanopsis patelliformis - Dan-ran Bian; Han Xue; Chun-gen Piao; Yong Li (Antonie van Leeuwenhoek, 2020)

Neo-debromoaplysiatoxin C, with new structural rearrangement, derived from debromoaplysiatoxin - Yang-Hua Tang; Ting-Ting Liang; Ting-Ting Fan; Lawrence Jordan Keen; Xiao-Dan Zhang; Lin Xu; Qi Zhao; Rong Zeng; Bing-Nan Han (Natural Product Research, 2020)

Association between the IL-6, IL-10, and TNFα gene polymorphisms and preterm-birth in Korean women - Seung Hun Han; Noo Ri Lee; Hyung Jun Kim; Yun Dan Kang; Jong Soo Kim; Jin Wan Park; Han Jun Jin (Genes & Genomics, 2020)

Long interpregnancy interval and adverse perinatal outcomes: A retrospective cohort study - Jing Lin; Han Liu; Dan-Dan Wu; Hong-Tao Hu; Hui-Hui Wang; Cheng-Liang Zhou; Xin-Mei Liu; Xiao-Jun Chen; Jian-Zhong Sheng; He-Feng Huang (Science China Life Sciences, 2020)

Synthesis, pharmacological evaluation and molecular docking of novel R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid as dual anti-inflammatory anti-platelet aggregation agents - Rong Rong; Rui-zhen Zhang; Xin Wang; Yu-han Dan; Yun-li Zhao; Zhi-guo Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Evaluation of the relationship between DNA methylation status and heterosis in soybean with MethylRAD technique - Baixing Song; Yuanqian Wang; Songnan Yang; Xueying Li; Xiao Han; Sujie Fan; Abraham Lamboro; Dan Yao; Jing Qu; Zhuo Zhang; Yang Song; Jun Zhang (Euphytica, 2020)

Disruption of cytochrome P450 enzymes in the liver and small intestine in chicken embryos in ovo exposed to glyphosate - Mohamed Ahmed Fathi; Guofeng Han; Ruifen Kang; Dan Shen; Jiakun Shen; Chunmei Li (Environmental Science and Pollution Research, 2020)

Diffusion MRI revealed altered inter-hippocampal projections in the mouse brain after intrauterine inflammation - Dan Wu; Jun Lei; Han Xie; Jie Dong; Irina Burd (Brain Imaging and Behavior, 2020)

Microbial methane production is affected by secondary metabolites in the heartwood of living trees in upland forests - Huan-Long Li; Xi-Mei Zhang; Feng-Dan Deng; Xing-Guo Han; Chun-Wang Xiao; Shi-Jie Han; Zhi-Ping Wang (Trees, 2020)

Nonlinear responses of soil nematode community composition to increasing aridity - Dan Xiong; CunZheng Wei; E. R. Jasper Wubs; G. F. Veen; Wenju Liang; Xiaobo Wang; Qi Li; Wim H. Van der Putten; Xingguo Han (Global Ecology and Biogeography, 2020)
Aim Increasing aridity under global change is predicted to have a profound impact on the structure and functioning of terrestrial ecosystems, yet we have a poor understanding of how belowground communities respond. In order to understand the longer term responses of different trophic levels in the soil food web to increasing aridity, we investigated the abundance, richness and community similarity of the soil nematode community along a 3,200 km aridity gradient. Location A transect across semi‐arid and arid grasslands in Northern China, where the aridity ranges from .43 to .97. Time period July and August 2012. Major taxa studied Soil‐borne Nematoda. Methods We used generalized additive (mixed) models to analyse the abundance, richness and community similarity patterns of soil nematodes. We used structural equation modelling (SEM) to disentangle the direct and indirect environmental drivers (aridity, soil and plant variables) of the nematode community. Results The abundance, richness and similarity of nematode communities declined nonlinearly with increasing aridity. The most pronounced decline in nematode richness and community similarity occurred in arid conditions (aridity > .80). However, the shape of the response to aridity differed among nematode feeding groups. In arid conditions, the abundance and richness of bacterial feeders were less sensitive to changes in aridity than for fungal feeders. The SEM analysis revealed that nematode community responses to aridity were not mediated via changes in plant and soil variables, but instead were affected directly by aridity. Main conclusions Our results showed that in mesic grasslands, increasing aridity primarily caused a decline in nematode abundance, whereas increasing aridity in xeric grasslands led to a loss of nematode diversity. The nonlinear responses of nematodes to aridity could also result in nonlinear shifts in ecosystem functioning, because soil nematodes operate at various trophic levels in the soil food web, thereby influencing the performance of plants, soil biodiversity and biogeochemical cycling.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Identification and classification of differentially expressed genes in pyrethroid-resistant Culex pipiens pallens - Na Xu; Xiao-Hong Sun; Zhi-Han Liu; Yang Xu; Yan Sun; Dan Zhou; Bo Shen; Chang-Liang Zhu (Molecular Genetics and Genomics, 2019)

Anti-secretogranin III therapy of oxygen-induced retinopathy with optimal safety - Fen Tang; Michelle E. LeBlanc; Weiwen Wang; Dan Liang; Ping Chen; Tsung-Han Chou; Hong Tian; Wei Li (Angiogenesis, 2019)

An endophytic fungus from Trichoderma harzianum SWUKD3.1610 that produces nigranoic acid and its analogues - MeiJun Han; Dan Qin; TianTian Ye; Xiao Yan; JunQi Wang; XiaoXiang Duan; JinYan Dong (Natural Product Research, 2019)

Enhanced nitrogen removal of coal pyrolysis wastewater with low COD to nitrogen ratio by partial nitrification-denitrification bioprocess assisted with polycaprolactone - Zhengwen Zhang; Chunyan Xu; Dan Zhong; Yuxing Han; Hongjun Han; Mengqi Zheng; Hao Zhu (Environmental Science and Pollution Research, 2019)

How forest gaps shaped plant diversity along an elevational gradient in Wolong National Nature Reserve? - Li Chen; Wangya Han; Dan Liu; Guohua Liu (Journal of Geographical Sciences, 2019)

Structural properties and antioxidant activities of polysaccharide from fruit bodies of Pholiota nameko - Zhen-Yuan Zhu; Li-Chao Pan; Dan Han; Hui-qing Sun; Li-Jing Chen (Natural Product Research, 2019)

Evaluating Walnut (Juglans spp.) for resistance to walnut blight and comparisons between artificial inoculation assays and field studies - Shijiao Jiang; Shan Han; Dan He; Guangli Cao; Fan Zhang; Xueqin Wan (Australasian Plant Pathology, 2019)

Treatment with MQA, a Derivative of Caffeoylquinic Acid, Provides Neuroprotective Effects against Cerebral Ischemia Through Suppression of the p38 Pathway and Oxidative Stress in Rats - Long Chen; Dan-ni Liu; Yu Wang; Xue-ying Liu; Shuai Han; Ke Zhang; Guo-yu Li; Xing Tian; Hang-yu Wang; Jin-hui Wang (Journal of Molecular Neuroscience, 2019)

Characteristics and management modes of domestic waste in rural areas of developing countries: a case study of China - Zhiyong Han; Changwen Ye; Yu Zhang; Zeng Dan; Zeyan Zou; Dan Liu; Guozhong Shi (Environmental Science and Pollution Research, 2019)

A Literature Review of Blood-Disseminated P. marneffei Infection and a Case Study of this Infection in an HIV-Negative Child with Comorbid Eosinophilia - Xiu-jing Han; Dan-hong Su; Jian-yun Yi; Ya-wei Zou; Yu-ling Shi (Mycopathologia, 2019)

Viral metagenomics analysis and eight novel viral genomes identified from the Dushanzi mud volcanic soil in Xinjiang, China - Dan-Ting Yu; Ji-Zheng He; Li-Mei Zhang; Li-Li Han (Journal of Soils and Sediments, 2019)

Report of a chiton in the genus Leptochiton (Lepidopleurida: Lepidopleurina: Leptochitonidae) from the Yap Trench in the West Pacific Ocean - Chunsheng Wang; Yadong Zhou; Dan Jiang; Jie Han (Acta Oceanologica Sinica, 2018)

Bioactive furanocoumarins from the stems and leaves of Clausena hainanensis - Yan-Lei Ma; Chao Zhang; Wan-Hui Zhao; Shi Shi; Dan-Nv He; Pan Zhang; Xiao-Hong Liu; Ting-Ting Han; Yan-Hui Fu; Yan-Ping Liu (Natural Product Research, 2018)

Proteomics analysis reveals marker proteins for minor vein initiation in rice leaf - Dan Feng; Yanwei Wang; Tiegang Lu; Zhiguo Zhang; Xiao Han (Functional & Integrative Genomics, 2018)

Development and evaluation of a rapid recombinase polymerase amplification assay for the detection of human enterovirus 71 - Dan Yin; Yanan Zhu; Kaifeng Wang; Jing Wang; Xiru Zhang; Min Han; Yaqing He; Qing Chen; Guifang Hu (Archives of Virology, 2018)

Changes in Skeletal Muscle and Body Weight on Sleeping Beauty Transposon-Mediated Transgenic Mice Overexpressing Pig mIGF-1 - Bo Gao; Wei Wang; Han Wu; Cai Chen; Dan Shen; Saisai Wang; Wei Chen; Li Zhang; Shuheng Chan; Chengyi Song (Biochemical Genetics, 2018)

Exploring inhibition mechanism and nature of lipase by Ligupurpuroside A extracted from Ku-Ding tea - Yu Fan; Yang Xu; Qing-Guo Han; Liang-Liang Shen; Hong Xu; Zhi-Bing Wu; Xu Xu; Ming Ying; Zhen-Dan He; Zhang-Li Hu (Medicinal Chemistry Research, 2018)

Combined topomer CoMFA and hologram QSAR studies of a series of pyrrole derivatives as potential HIV fusion inhibitors - Dan Han; Jianjun Tan; Ziyun Zhou; Chunhua Li; Xiaoyi Zhang; Cunxin Wang (Medicinal Chemistry Research, 2018)

Effects of vegetation coverage and seasonal change on soil microbial biomass and community structure in the dry-hot valley region - Han Wu; Dong-hong Xiong; Liang Xiao; Su Zhang; Yong Yuan; Zheng-an Su; Bao-jun Zhang; Dan Yang (Journal of Mountain Science, 2018)

Risk factors, outcomes and genotypes of carbapenem-nonsusceptible Klebsiella pneumoniae bloodstream infection: a three-year retrospective study in a large tertiary hospital in Northern China - Si-Han Zheng; Sheng-Ji Cao; Hui Xu; Dan Feng; Li-Ping Wan; Guang-Jie Wang; Xiao-Guang Xiao (Infectious Diseases, 2018)

Analysis of the function of KIF3A and KIF3B in the spermatogenesis in Boleophthalmus pectinirostris - Yong-Qiang Zhao; Dan-Li Mu; Di Wang; Ying-Li Han; Cong-Cong Hou; Jun-Quan Zhu (Fish Physiology and Biochemistry, 2018)

Study on the relationship between genetic variation of DNA methylation and heterosis in soybean leaves - Yuanqian Wang; Kaixin Zhang; Lifang Sun; Xiao Han; Sujie Fan; Xueying Li; Yiwei Qu; Dan Yao; Piwu Wang; Jun Zhang (Euphytica, 2018)

A comparison of amorphous calcium carbonate crystallization in aqueous solutions of MgCl2 and MgSO4: implications for paleo-ocean chemistry - Mei Han; Yanyang Zhao; Hui Zhao; Zuozhen Han; Huaxiao Yan; Bin Sun; Ruirui Meng; Dingxiang Zhuang; Dan Li; Binwei Liu (Mineralogy and Petrology, 2018)

Metrical Consistency NMF for Predicting Gene–Phenotype Associations - Shuai Han; Hong Cai; Dan Che; Yaogong Zhang; Yalou Huang; Maoqiang Xie (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Silicon alleviates cadmium toxicity in wheat seedlings (Triticum aestivum L.) by reducing cadmium ion uptake and enhancing antioxidative capacity - Zhenya Shi; Suqin Yang; Dan Han; Zhen Zhou; Xuanzhen Li; Ye Liu; Biao Zhang (Environmental Science and Pollution Research, 2018)

Significant genetic association of a functional TFPI variant with circulating fibrinogen levels and coronary artery disease - Duraid Hamid Naji; Chengcheng Tan; Fabin Han; Yuanyuan Zhao; Junhan Wang; Dan Wang; Jingjing Fa; Sisi Li; Shanshan Chen; Qiuyun Chen; Chengqi Xu; Qing K. Wang (Molecular Genetics and Genomics, 2018)

Effect of corticosteroids on atrial fibrillation after catheter ablation: a meta-analysis - Sanjay Jaiswal; Xian-bao Liu; Qu-cheng Wei; Ying-hao Sun; Li-han Wang; Liu-guang Song; Dan-dan Yang; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2018)

Development of a stable Japanese encephalitis virus replicon cell line for antiviral screening - Qiu-Yan Zhang; Xiao-Dan Li; Si-Qing Liu; Cheng-Lin Deng; Bo Zhang; Han-Qing Ye (Archives of Virology, 2017)

A new catechin derivative from the fruits of Rosa sterilis S. D. Shi - Xu-Lu Luo; Han-Long Dan; Na Li; Yong-He Li; Ying-Jun Zhang; Ping Zhao (Natural Product Research, 2017)

A genetic variant in the placenta-derived MHC class I chain-related gene A increases the risk of preterm birth in a Chinese population - Junjiao Song; Jing Li; Han Liu; Yuexin Gan; Yang Sun; Min Yu; Yongjun Zhang; Fei Luo; Ying Tian; Weiye Wang; Jun Zhang; Julian Little; et al. (Human Genetics, 2017)

Basidiomycete‐specific PsCaMKL1 encoding a CaMK‐like protein kinase is required for full virulence of Puccinia striiformis f. sp. tritici - Min Jiao; Dan Yu; Chenglong Tan; Jia Guo; Dingyun Lan; Ershang Han; Tuo Qi; Ralf Thomas Voegele; Zhensheng Kang; Jun Guo (Environmental Microbiology, 2017)
Summary Calcium/calmodulin‐dependent kinases (CaMKs) are Ser/Thr protein kinases (PKs) that respond to changes in cytosolic free Ca 2+ and play diverse roles in eukaryotes. In fungi, CAMKs are generally classified into four families CAMK1, CAMKL, RAD53 and CAMK‐Unique. Among these, CAMKL constitutes the largest family. In some fungal plant pathogens, members of the CaMKL family have been shown to be responsible for pathogenesis. However, little is known about their role(s) in rust fungi. In this study, we functionally characterized a novel PK gene, PsCaMKL1 , from Puccinia striiformis f. sp. tritici ( Pst ). Ps CaMKL1 belongs to a group of PKs that is evolutionarily specific to basidiomyceteous fungi. Ps CaMKL1 shows little intra‐species polymorphism between Pst isolates. PsCaMKL1 transcripts are highly elevated at early infection stages, whereas gene expression is downregulated in barely germinated urediospores under KN93 treatment. Overexpression of PsCaMKL1 in fission yeast increased resistance to environmental stresses. Knock down of PsCaMKL1 using host‐induced gene silencing (HIGS) reduced the virulence of Pst accompanied by reactive oxygen species (ROS) accumulation and a hypersensitive response. These results suggest that Ps CaMKL1 is a novel pathogenicity factor that exerts it virulence function by regulating ROS production in wheat.

Temporal dynamics and vertical variations in stem CO2 efflux of Styphnolobium japonicum - Fengsen Han; Xiaolin Wang; Hongxuan Zhou; Yuanzheng Li; Dan Hu (Journal of Plant Research, 2017)

Bdellovibrio and like organisms promoted growth and survival of juvenile abalone Haliotis discus hannai Ino and modulated bacterial community structures in its gut - Yanbiao Guo; Qi Pan; Shiqi Yan; Yuhong Chen; MingJia Li; Dan Chen; Hongcao Han; Bing Wu; Junpeng Cai (Aquaculture International, 2017)

Tolerance and stress response of sclerotiogenic Aspergillus oryzae G15 to copper and lead - Dan-Dan Long; Rong-Rong Fu; Jian-Rong Han (Folia Microbiologica, 2017)

Single-Prolonged-Stress-Induced Changes in Autophagy-Related Proteins Beclin-1, LC3, and p62 in the Medial Prefrontal Cortex of Rats with Post-traumatic Stress Disorder - Shilei Zheng; Fang Han; Yuxiu Shi; Lili Wen; Dan Han (Journal of Molecular Neuroscience, 2017)

Characteristics of Aerococcus viridans isolated from bovine subclinical mastitis and its effect on milk SCC, yield, and composition - Meng Sun; Jian Gao; Tariq Ali; Dan Yu; Shiyao Zhang; Saeed U. Khan; Séamus Fanning; Bo Han (Tropical Animal Health and Production, 2017)

Unique community structure of viruses in a glacier soil of the Tianshan Mountains, China - Li-Li Han; Dan-Ting Yu; Li-Mei Zhang; Jun-Tao Wang; Ji-Zheng He (Journal of Soils and Sediments, 2017)

Cloning and expression analysis of zygote arrest 1 (Zar1) in New Zealand white rabbits - DAN WANG; SHU-YU XIE; WEI ZHANG; CAI-XIA SUN; TAO HUANG; AN-SI WANG; XUE-LEI HAN; GUI-RONG SUN; MING LI (Journal of Genetics, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Salidroside accelerates fracture healing through cell-autonomous and non-autonomous effects on osteoblasts - Xiao Qin Guo; Lin Qi; Jing Yang; Yue Wang; Chuan Wang; Zong Min Li; Ling Li; Ye Qu; Dan Wang; Ze Min Han (Cell and Tissue Research, 2017)

The role of apparent diffusion coefficient values in characterization of solid focal liver lesions: a prospective and comparative clinical study - Dawei Yang; Jie Zhang; Dan Han; Erhu Jin; Zhenghan Yang (Science China Life Sciences, 2017)

Molecular epidemiology and phylogenetic analysis of HA gene of influenza A(H1N1)pdm09 strain during 2010–2014 in Dalian, North China - Yan Han; Nan Sun; Qiu-yue Lv; Dan-hong Liu; Da-peng Liu (Virus Genes, 2016)

A combined liquid chromatography-triple-quadrupole mass spectrometry method for the residual detection of veterinary drugs in porcine muscle, milk, and eggs - Dan Zhang; Zee-Yong Park; Jin-A Park; Seong-Kwan Kim; Daun Jeong; Sang-Hyun Cho; Jae-Han Shim; Jin-Suk Kim; A. M. Abd El-Aty; Ho-Chul Shin (Environmental Monitoring and Assessment, 2016)

Enhanced degradation of trichloroethylene using bentonite-supported nanoscale Fe/Ni and humic acids - Shihe Wang; Yitong Han; Xi Cao; Dan Zhao; Dezhong Yang; Jiawei Chen (Environmental Chemistry Letters, 2016)

Experimental Investigation on Non-Darcian Flow in Unbound Graded Aggregate Material of Highway Pavement - Han-Cheng Dan; Lin-Hua He; Bo Xu (Transport in Porous Media, 2016)

QTL mapping of flag leaf traits in common wheat using an integrated high-density SSR and SNP genetic linkage map - Qiuhong Wu; Yongxing Chen; Lin Fu; Shenghui Zhou; Jiaojiao Chen; Xiaojie Zhao; Dong Zhang; Shuhong Ouyang; Zhenzhong Wang; Dan Li; Guoxin Wang; Deyun Zhang; et al. (Euphytica, 2016)

Cannabinoid CB1 receptor signaling dichotomously modulates inhibitory and excitatory synaptic transmission in rat inner retina - Xiao-Han Wang; Yi Wu; Xiao-Fang Yang; Yanying Miao; Chuan-Qiang Zhang; Ling-Dan Dong; Xiong-Li Yang; Zhongfeng Wang (Brain Structure and Function, 2016)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

Preface: the WinMon.BE 2013 conference: steps towards an efficient and effective offshore wind farm environmental impact assessment - Steven Degraer; Jennifer Dannheim; Andrew B. Gill; Han Lindeboom; Dan Wilhelmsson (Hydrobiologia, 2015)

Offshore wind park monitoring programmes, lessons learned and recommendations for the future - Han Lindeboom; Steven Degraer; Jennifer Dannheim; Andrew B. Gill; Dan Wilhelmsson (Hydrobiologia, 2015)

Attenuated Blood-Brain Barrier Dysfunction by XQ-1H Following Ischemic Stroke in Hyperlipidemic Rats - Weirong Fang; Lan Sha; Nandani Darshika Kodithuwakku; Jie Wei; Rui Zhang; Dan Han; Lishun Mao; Yunman Li (Molecular Neurobiology, 2015)

Isolation and Characterization of a Novel SOMATIC EMBRYOGENESIS RECEPTOR KINASE Gene Expressed in the Fern Adiantum capillus-veneris During Shoot Regeneration In Vitro - Xia Li; Yu-Han Fang; Jing-Dan Han; Shu-Nong Bai; Guang-Yuan Rao (Plant Molecular Biology Reporter, 2015)

Analysis of the Drought Stress-Responsive Transcriptome of Black Cottonwood (Populus trichocarpa) Using Deep RNA Sequencing - Sha Tang; Yan Dong; Dan Liang; Zhoujia Zhang; Chu-Yu Ye; Peng Shuai; Xiao Han; Ying Zhao; Weilun Yin; Xinli Xia (Plant Molecular Biology Reporter, 2015)

Distribution of Yeast Isolates from Invasive Infections and Their In Vitro Susceptibility to Antifungal Agents: Evidence from 299 Cases in a 3-Year (2010 to 2012) Surveillance Study - Wei Li; Yu-an Hu; Fang-qiu Li; Li-ning Shi; Hai-feng Shao; Mei Huang; Ying Wang; Dan-dan Han; Hong Liao; Chun-fang Ma; Guo-yong Zhang (Mycopathologia, 2015)

Growth, V uptake, and antioxidant enzymes responses of chickpea (Cicer arietinum L.) genotypes under vanadium stress - Muhammad Imtiaz; Shuxin Tu; Zhijian Xie; Dan Han; Muhammad Ashraf; Muhammad Shahid Rizwan (Plant and Soil, 2015)

Regional integrated environmental modeling system: development and application - Shuyu Wang; Congbin Fu; Helin Wei; Yun Qian; Zhe Xiong; Jinming Feng; Deming Zhao; Li Dan; Zhiwei Han; Bingkai Su; Ming Zhao; Yaocun Zhang; et al. (Climatic Change, 2015)

The effects of complete submergence on the morphological and biomass allocation response of the invasive plant Alternanthera philoxeroides - Shufeng Fan; Haihao Yu; Chunhua Liu; Dan Yu; Yuqin Han; Ligong Wang (Hydrobiologia, 2015)

Phytoplankton and chlorophyll a relationships with ENSO in Prydz Bay, East Antarctica - HaiSheng Zhang; ZhengBing Han; Jun Zhao; PeiSong Yu; ChuanYu Hu; WeiPing Sun; Dan Yang; GenHai Zhu; Bing Lu; Hans-UIrich Peter; Walter Vetter (Science China Earth Sciences, 2014)

The study of regulatory effects of Pdx-1, MafA and NeuroD1 on the activity of porcine insulin promoter and the expression of human islet amyloid polypeptide - Xiao-Dan Liu; Jin-Xue Ruan; Ji-Han Xia; Shu-Lin Yang; Jun-Hua Fan; Kui Li (Molecular and Cellular Biochemistry, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Effect of copper-induced oxidative stress on sclerotial differentiation and antioxidant properties of Penicillium thomii PT95 strain - Ze-Qing Zhang; Wen-Jing Zhao; Dan-Dan Long; Lin-Ru Niu; Jian-Rong Han (World Journal of Microbiology and Biotechnology, 2014)

Reflection and Transmission of Plane Waves at a Water–Porous Sediment Interface with a Double-Porosity Substrate - Dan-Dan Lyu; Jin-Ting Wang; Feng Jin; Chu-Han Zhang (Transport in Porous Media, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

A Simple One-Step PCR Walking Method and Its Application of Bacterial rRNA for Sequencing Identification - Hongfa Zhang; Chunping You; Jing Ren; Dan Xu; Mei Han; Wenyan Liao (Current Microbiology, 2014)

Selection and Characterization of a Peptide Specifically Targeting to Gastric Cancer Cell Line SGC-7901 Using Phage Display - Han Wang; Rui Li; Caixia Ma; Shaoying Lu; Dan Zhang; Yonge Guo; ChunYan Li; Jinling Wu; Qixuan Wang; Jinhui Xu; Yanyan Hu; Yuen Liu; et al. (International Journal of Peptide Research and Therapeutics, 2014)

Cloning and molecular characterization of a myosin light chain gene from Puccinia striiformis f. sp. tritici - Jie Liu; Li-Na Han; Qiong Zhang; Qiu-Ling Wang; Qing Chang; Hua Zhuang; Jia Liu; Man Li; Dan Yu; Zhen-Sheng Kang (World Journal of Microbiology and Biotechnology, 2014)

A Simple One-Step PCR Walking Method and Its Application of Bacterial rRNA for Sequencing Identification - Hongfa Zhang; Chunping You; Jing Ren; Dan Xu; Mei Han; Wenyan Liao (Current Microbiology, 2014)

Effects of Monogalactoglycerolipid Deficiency and Diacylglycerol Acyltransferase Overexpression on Oil Accumulation in Transgenic Tobacco - Han-Ying Wu; Chao Liu; Min-Chun Li; Ming-Ming Zhao; Dan Gu; Yi-Nong Xu (Plant Molecular Biology Reporter, 2013)

Influence of different fertilization regimes on plant-parasitic nematodes in the black soil region of Northeast China - Fengjuan Pan; Yanli Xu; Neil B. McLaughlin; Wei Liu; Xiaozeng Han; Lili Zhan; Dan Zhao (Phytoparasitica, 2013)

Transfer of Cd, Pb, and Zn to water spinach from a polluted soil amended with lime and organic materials - Defei Han; Dan Luo; Yanhui Chen; Guo Wang (Journal of Soils and Sediments, 2013)

Synthesis of novel 4-thiazolidione derivatives as antibacterial agents against drug-resistant Staphylococcus epidermidis - Dan Zhao; Huayong Liu; Likang Zheng; Guozhen He; Di Qu; Shiqing Han (Medicinal Chemistry Research, 2013)

Performance and leaching analysis of a novel coal sludge-based backfill material - Yuan Yao; Henghu Sun; Shushu Jiang; Rui Zhang; Dan Su; Chao Feng; Xiaoyuan Han (Clean Technologies and Environmental Policy, 2013)

Re-Examination of the Genotoxic Activity of Water Taken From the Songhua River in P. R. China - Jia Yu; Hong-Wei Dong; Li-Tian Shi; Hui-Ling Jiang; Jian-Wen Yu; Qian-Wen Zhao; Shi-Chun Cai; Dan Han; Xuan-Yue Tang; Jia-Ren Liu (Archives of Environmental Contamination and Toxicology, 2013)

In vitro isolation and cultivation of rabbit tracheal epithelial cells using tissue explant technique - Hong-Can Shi; Dan Lu; Hai-Jia Li; Shi Han; Yan-Jun Zeng (In Vitro Cellular & Developmental Biology - Animal, 2013)

Efficient and stable rescue of classical swine fever virus from cloned cDNA using an RNA polymerase II system - Chao Li; Junhua Huang; Yongfeng Li; Fan He; Dan Li; Yuan Sun; Wen Han; Su Li; Hua-Ji Qiu (Archives of Virology, 2013)

Beta amyloid, tau, neuroimaging, and cognition: sequence modeling of biomarkers for Alzheimer’s Disease - S. Duke Han; Jonathan Gruhl; Laurel Beckett; Hiroko H. Dodge; Nikki H. Stricker; Sarah Farias; Dan Mungas (Brain Imaging and Behavior, 2012)

QTL analysis of soybean seed weight across multi-genetic backgrounds and environments - Yingpeng Han; Dongmei Li; Dan Zhu; Haiyan Li; Xiuping Li; Weili Teng; Wenbin Li (Theoretical and Applied Genetics, 2012)

Monocyte to macrophage differentiation-associated (MMD) positively regulates ERK and Akt activation and TNF-α and NO production in macrophages - Qiang Liu; Jin Zheng; Dan-Dan Yin; Jie Xiang; Fei He; Yao-Chun Wang; Liang Liang; Hong-Yan Qin; Li Liu; Ying-Min Liang; Hua Han (Molecular Biology Reports, 2012)

Agricultural reclamations in Xiliao River Valley, China since the Holocene - Maoli Han; Yuhui Zhao; Dan Zhang (Journal of Geographical Sciences, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

Mutations in exons of the CYP17-II gene affect sex steroid concentration in male Japanese flounder (Paralichthys olivaceus) - Ruiqin Ma; Feng He; Haishen Wen; Jifang Li; Bao Shi; Dan Shi; Miao Liu; Weijie Mu; Yuanqing Zhang; Jian Hu; Weiguo Han; Jianan Zhang; et al. (Journal of Ocean University of China, 2012)

Isomer-specific effects of conjugated linoleic acid on proliferative activity of cultured neural progenitor cells - Han Wang; Tianqing Liu; Jihui Wang; Yanli Qi; Dan Ge; Shui Guan (Molecular and Cellular Biochemistry, 2011)

Erratum to: A complete genome assembly of Glaciecola mesophila sp. nov. sequenced by using BIGIS-4 sequencer system - LiNa Yuan; LuFeng Ren; YunTao Li; WeiJing Han; Yong Yu; YaNan Chu; GuiMing Liu; Dan Yu; MingJing Teng; Liang Wang; XuMin Wang; XiaoGuang Zhou; et al. (Science China Life Sciences, 2011)

A complete genome assembly of Glaciecola mesophila sp. nov. sequenced by using BIGIS-4 sequencer system - LiNa Yuan; LuFeng Ren; YunTao Li; WeiJing Han; Yong Yu; YaNan Chu; GuiMing Liu; Dan Yu; MingJing Teng; Liang Wang; XuMin Wang; XiaoGuang Zhou; et al. (Science China Life Sciences, 2011)

Study on polymerization effect of polyembryony genes by SSCP marker and family trees in Chinese goats - Guang Li; Xiaopeng An; Jinxing Hou; Ling Li; Dan Han; Mingming Yang; Yana Wang; Guangqin Zhu; Jiangang Wang; Yuxuan Song; Bin Yun Cao (Molecular Biology Reports, 2011)

Construction of a framework map for Pinus koraiensis Sieb. et Zucc. using SRAP, SSR and ISSR markers - Min-Min Chen; Fujuan Feng; Xin Sui; Mai-He Li; Dan Zhao; Shijie Han (Trees, 2010)

Notch signaling maintains proliferation and survival of the HL60 human promyelocytic leukemia cell line and promotes the phosphorylation of the Rb protein - Guo-Hui Li; Yu-Zhen Fan; Xiao-Wei Liu; Bing-Fang Zhang; Dan-Dan Yin; Fei He; Si-Yong Huang; Zhi-Jie Kang; Heng Xu; Qiang Liu; Yan-Lan Wu; Xiao-Li Niu; et al. (Molecular and Cellular Biochemistry, 2010)

Spontaneous Rhythmic Inward Currents Recorded in Interstitial Cells of Rabbit Portal Vein - Xu Huang; Dan Zhao; Zuo-Yu Wang; Ming-Liang Zhang; Zhi-Qiang Yan; Yan-Fei Han; Hong-Li Lu; Wen-Xie Xu; Zong-Lai Jiang (Cell Biochemistry and Biophysics, 2010)

A single-nucleotide polymorphism of the TNFAIP3 gene is associated with systemic lupus erythematosus in Chinese Han population - Li-Qiong Cai; Zai-Xing Wang; Wen-Sheng Lu; Jian-Wen Han; Liang-Dan Sun; Wen-Hui Du; Shu-Mei Zhang; Xian-Bo Zuo; Xue-Jun Zhang; Sen Yang (Molecular Biology Reports, 2010)

Study and Application of the Interaction Between Asymmetrical Porphyrin and Ascorbic Acid - Shuting Sun; Dan Wu; Qin Wei; Yanyan Han; Xin Chen; Yunxia Shen; Peihua Zhu; Bin Du (Journal of Fluorescence, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Above- and belowground competition between two submersed macrophytes - Jin-Wang Wang; Dan Yu; Wen Xiong; Yu-Qin Han (Hydrobiologia, 2008)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

Development of combined biological technology for treatment of high-strength organic wastewater and results of case studies - Nanqi Ren; Aijie Wang; Hongjun Han; Fang Ma; Jie Ding; Yue Shi; Dan Zhao (Journal of Ocean University of China, 2006)

Regional carrying capacity: case studies of Bohai Rim area - Yu Dan-lin; Mao Han-ying (Journal of Geographical Sciences, 2002)